White wine, sparkling white wine and black caviar – The sensory experience of pairing of flavours - K. Wendin; B. Collin; S. Forsberg; H. Scander; R. Albin; F. Åhrberg; T. Ranta (International Journal of Gastronomy and Food Science, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

A Review of 35 Years in Developing Constitutive Models for the Callovo-Oxfordian Claystone Behavior - M. N. Vu; G. Armand; J. Talandier; C. Plua; M. Souley; J. F. Shao; Z. Yu; J. B. Colliat; J. Vaunat; A. Gens; S. Olivella; F. Collin; et al. (Rock Mechanics and Rock Engineering, 2026)

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

Orogens and detritus: unravelling the Mesoproterozoic tectonic geography of northern Australia through coupled detrital thermo- and geo-chronometers - B. Yang; A. S. Collins; M. L. Blades; F. Jourdan (Australian Journal of Earth Sciences, 2026)

Disseminated multidrug-resistant Salmonella enterica serovar Dublin infection associated with plasmid-borne CMY-2 gene in a patient with travel to a farm in Mexico - Mackenzie E. Collins; Lilian Fung; Timothy F. Brewer; Shangxin Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Disseminated Salmonella enterica infections represent a severe form of non-typhoidal salmonellosis increasingly complicated by antimicrobial resistance. We describe a case of disseminated non-typhoidal Salmonella in a man presenting with septic shock concerning for a thoracoabdominal endovascular graft infection with involvement of the urinary and respiratory tracts and thoracic skeleton. Hybrid whole-genome sequencing identified Salmonella enterica serovar Dublin and two significant plasmids, an IncC multidrug resistance plasmid harboring bla CMY−2 , bla TEM−206 , tet ( A ), and sul2 and an IncFII(S)/IncX1 virulence plasmid containing a spvA - D / spvR operon associated with systemic infection. This case highlights a potential food-borne or zoonotic acquisition of invasive, plasmid-mediated AmpC-producing Salmonella Dublin.

Title: The evaluation of ruminal undegradable protein supplementation level on growth performance and ovarian development in beef heifers grazing native rangelands. - Taylor N. Andrews; Maria K. Chavez; Emily A. Melchior; Collin Anderson; Alexis B. Tamez; Shelby L. Rosasco; Shad H. Cox; Richard L. Dunlap; Robert A. Cushman; Jennifer A. Hernandez-Gifford; Eric J. Scholljegerdes; Adam F. Summers (Animal Reproduction Science, 2026)

A Global Review of Bycatch Reduction Technology Assessments: Revealing Gaps in Fisher‐Focused Metrics - Cindy Vargas; James P. Collins; Jesse F. Senko (Fish and Fisheries, 2026)
Global fisheries support livelihoods, food security and economies, but the incidental capture of non‐target species—termed bycatch—remains a key conservation challenge. We compiled peer‐reviewed published studies to assess metrics used to evaluate the effectiveness of bycatch reduction technologies and gear modifications (BRTs) for reducing air‐breathing marine megafauna bycatch in global passive fisheries. We assessed 196 studies, including assessments in operational fisheries and controlled experiments, from 114 published articles between 1997 and 2024. These studies tested 28 types of BRTs across five fishing gears. Changes in bycatch and target catch were assessed in 94.4% and 73% of all studies, respectively. By contrast, only 6.6% of studies assessed catch value. We identified and evaluated seven fisher‐focused metrics that were divided into quantitative and anecdotal evidence describing how the application of BRTs affects fishers. Relative to quantitative assessments, 9.2% of all studies quantified effects on fishing gear, 8.7% quantified BRT cost, 4.1% quantified economic impact, 3.1% quantified fisher safety, 3.1% quantified BRT ease of use, 2% quantified operational efficiency and 1% quantified fisher perceptions of BRT efficacy. Relative to anecdotal evidence, 10.7% of all studies reported on ease of use, 7.1% on BRT cost, 6.6% on fisher perceptions of efficacy, 3.1% on effects on fishing gear, 1.5% on effects on fisher safety and 0.5% on both operational efficiency and economic impact. Across diverse regions and timeframes, our analysis highlights a persistent lack of fisher‐focused metrics in BRT research, emphasising the need for more holistic evaluations that consider fisher wellbeing.

Heme Iron Polypeptide Resolves Iron-deficiency Anemia in Rats and Mice - Yue He; Jacob S. Shine; Sitara Sriram; Melissa Fraga; Li-Ying Kuo; Jennifer K. Lee; Xiaojing Yuan; Iqbal Hamza; James F. Collins (Biological Trace Element Research, 2026)

Who owns the minerals in polluted mine water? Property rights and institutional barriers to rare earth elements recovery from acid mine drainage - Hélène F. Nguemgaing; Alan R. Collins (Resources Policy, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Incorporating fire severity mapping into fuel accumulation curves - Christopher E. Gordon; Luke Collins; Meaghan Jenkins; Brett P. Murphy; Trung H. Nguyen; Owen F. Price; Liubov Volkova; Christopher J. Weston; Rachael H. Nolan (Science of The Total Environment, 2026)

Correction: A framework for detection and attribution of regional precipitation change: application to the United States historical record - Mark D. Risser; William D. Collins; Michael F. Wehner; Travis A. O’Brien; Christopher J. Paciorek; John P. O’Brien; Christina M. Patricola-DiRosario; Huanping Huang; Paul A. Ullrich; Burlen Loring (Climate Dynamics, 2026)

Correction: Quantifying the influence of natural climate variability on in situ measurements of seasonal total and extreme daily precipitation - Mark D. Risser; Michael F. Wehner; John P. O’Brien; Christina M. Patricola-DiRosario; Travis A. O’Brien; William D. Collins; Christopher J. Paciorek; Huanping Huang (Climate Dynamics, 2026)

An Equatorial Hemispheric Barrier Shapes the Diversification of Migratory Belenois Butterflies - Anna Janiczek; Aleix Palahí; Leonardo Dapporto; Gemma Díaz‐Martínez; Vazrick Nazari; Aurora García‐Berro; Farid Bahleman; Steve C. Collins; Perpetra Akite; Michael F. Braby; Niclas Backström; Roger Vila; et al. (Molecular Ecology, 2026)
Biogeographic barriers are typically considered prominent geographic features that block or severely restrict dispersal and gene flow. However, mating barriers can also emerge within continuous suitable habitats, driven by ecological or behavioural constraints. Migratory insects show an extraordinary capacity to traverse vast geographic ranges, as well as notable landscape features like mountains, deserts and oceans. Yet, their movements are not unrestricted: they are shaped by seasonal dynamics that dictate the feasibility of migration across these landscapes. Hemisphericity, the existence of inverted seasonal regimes and orientation cues in the two latitudinal hemispheres, has been proposed as a potential abiotic barrier involved in the diversification of migratory insects. Here, we use population genomic data to investigate patterns of diversification in migratory caper butterflies ( Belenois spp.) across Africa. We identify a striking phylogeographic break around the equator in Belenois aurota , and emerging population structure between northern and southern African populations in Belenois creona , consistent with migratory divides aligned with hemispheric barriers. These divergences largely predate the Last Glacial Maximum, when major environmental changes such as contractions‐expansions of equatorial rainforests and savannahs occurred. This reinforces the hypothesis that long‐term abiotic factors, such as hemisphericity, had a role in limiting north–south dispersal. Given the absence of detectable gene flow detected even in sympatric populations of B. aurota in their contact zone in Kenya, Uganda, and Tanzania, we argue that populations from the Northern and Southern Hemispheres represent different species, and reinstate the taxon Belenois syrinx (Wallengren, 1860) reinst. stat. for the Southern African lineage. Our findings provide genomic evidence of migratory divides in insects, which surprisingly emerge in the absence of physical barriers in the landscape, highlighting a role of hemisphere‐specific adaptations in driving reproductive isolation and diversification in migratory insects.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Superchilling storage reduces the growth and diversity of bacterial communities associated with Atlantic salmon (Salmo salar) fillets - P. Collin; M. Darsonval; O. Rué; F.T. Ndoye; G. Alvarez; F. Dubois-Brissonnet (Food Research International, 2026)

Positive feedbacks among biotic and abiotic stressors mediate whitebark pine decline - Sara J. Germain; Matthew F. Bekker; Savannah A. Collins-Key; Georg von Arx (Forest Ecology and Management, 2025)

Alternating self-administration sessions of cocaine and heroin impact drug-related motivation and vocalisations in rats - Kristian Adamatzky; Angharad C. Collins; Aldo Badiani; Bryan F. Singer (Psychopharmacology, 2025)
Rationale Animal models of addiction often study changes in motivation after repeated self-administration of a single drug. However, human users frequently consume multiple drugs, potentially altering their motivation and affective response. Objectives This study investigated how individual rats differentially self-administer cocaine and heroin, and whether motivation to take each drug was associated with affective states, as indicated by ultrasonic vocalisations (USVs). We also determined whether opioid antagonism (via naltrexone), which is known to decrease heroin-taking and associated USVs, also altered motivation and vocalisations for cocaine. Methods Male Lister Hooded rats, with surgically implanted catheters, self-administered cocaine and heroin on alternating days. Motivation was evaluated via drug intake escalation (fixed-ratio schedule), behavioural adaptation to dose reductions (behavioural economics), and progressive ratio breakpoints (with or without naltrexone). USVs were recorded and analysed using machine learning software (DeepSqueak). Results Rats escalated intake of both drugs during training. At the start of each session, rats rapidly self-administered cocaine or heroin; this drug-loading behaviour was associated with an increase in 50 kHz vocalisations. Rats altered their cocaine and heroin intake when drug doses decreased, and this was accompanied by reduced 50 kHz USVs. Lastly, naltrexone reduced progressive ratio breakpoints for heroin but not cocaine; naltrexone also decreased 50 kHz USVs for heroin (an effect which persisted). Conclusions Distinct patterns emerged in motivation and USVs between cocaine and heroin self-administration. Notably, USV frequency did not consistently align with motivation, especially when drug dosage changed. Future research may clarify this divergence.

Application of fin tissue for nonlethal stable isotope analysis of small-bodied fishes - Wade M. Wilson; Jane S. Rogosch; Scott F. Collins; Bart W. Durham; Kevin B. Mayes; Sarah M. Robertson (Environmental Biology of Fishes, 2025)
Stable isotopes are commonly used to characterize food web structure and resource use by aquatic organisms. White muscle is generally preferred for stable isotope analysis of fishes. However, obtaining white muscle tissue typically requires lethal take or invasive sampling techniques, which are undesirable for small-bodied species or those of conservation concern. We assessed the use of fish fin as a nonlethal alternative to muscle tissue for stable isotope analysis of four small-bodied fishes native to the upper Red River drainage of Texas and Oklahoma, USA: plains minnow Hybognathus placitus , prairie chub Macrhybopsis australis , Red River shiner Alburnops bairdi , and Red River pupfish Cyprinodon rubrofluviatilis . Fin isotope values were strong predictors of both δ 15 N and δ 13 C muscle isotope values (ANCOVA: δ 15 N: F 1,451 = 5312.09, P < 0.001; δ 13 C: F 1,451 = 7864.39, P < 0.001), although isotopic composition varied among species for δ 13 C ( F 3,451 = 4.29, P < 0.01). Species-specific regression models indicated positive linear relationships between fin and muscle isotope values (δ 15 N: P < 0.001, R 2 ≥ 0.80; δ 13 C: P < 0.001, R 2 ≥ 0.83) that did not vary significantly with body size or age of individuals. We suggest minimum total length thresholds for least destructive fin clipping at 70 mm, 62 mm, and 48 mm for plains minnow, prairie chub, and Red River pupfish, respectively. Nonlethal fin clipping may not be viable for Red River shiner within the size range reported here as multiple fins were required for routine analysis. Overall, we conclude that fin tissue may be used for δ 15 N and δ 13 C assessments to mitigate lethal take of imperiled, small-bodied fishes.

Associations between fishes (Actinopterygii: Teleostei) and anthozoans (Anthozoa: Hexacorallia) in epipelagic waters based on in situ records - Gabriel V. F. Afonso; G. David Johnson; R. Collins; Murilo N. L. Pastana (Journal of Fish Biology, 2025)
We formally describe the association of fishes and anthozoans in epipelagic waters, extending this relationship to beyond the benthos. In situ observations and photographs of Aluterus schoepfii , Ariomma regulus , Caranx cf. latus and Brama spp. swimming alongside or holding larval tube anemones (Cerianthidae and Arachnactidae) and larval zoanthids (Sphenopidae) were made during blackwater SCUBA dives off Palm Beach, Florida, USA, and off Punaauia, Tahiti, French Polynesia. We report and illustrate the behaviour of these interactions, and suggest an advantage for the anthozoans.

Evidence for the ‘growth-dilution’ of microplastics and microfibers in urban stream fish populations - Scott F. Collins; Lauren Soliz; Garrett Tucker; Andrea Norton (Science of The Total Environment, 2025)

State Laws Leveraging the Community Eligibility Provision to Build Healthy School Meals for All: A Content Analysis - Elizabeth Piekarz-Porter; Juliana Cohen; Rebecca M. Schermbeck; Julien Leider; Tanya Agurs-Collins; Jamie F. Chriqui (Journal of the Academy of Nutrition and Dietetics, 2025)

Teamwork makes the dream work: combining community science and expert-led surveys to study urban plant richness and composition - Sophie Taddeo; Erin F. Snyder; Elsa C. Anderson; Collin M. Porter; Tatiana M. Guider; Kayri Havens (Urban Ecosystems, 2025)
Maintaining diverse plant communities in cities is critical to meeting conservation goals and supporting human well-being. However, gaps persist in our understanding of the various factors that interact in urban environments to modulate plant richness, composition, and persistence. Elucidating these gaps would inform successful conservation efforts but requires extensive data to capture the many factors that impact ecological communities in time and space. These data are potentially available but vary in origin, quality, and accessibility. Professional scientists increasingly publish urban biodiversity studies, myriad community science projects engage participants in documenting nature, and local institutions often maintain species inventories. Combining these data sources could offer a more accurate portrait of urban biodiversity but requires understanding where sources overlap and leave gaps. To address this need, we use Cook County, Illinois – the second most populous county in the United States – as a case study to assess how combining peer-reviewed studies, community science, and grey literature can capture urban plant biodiversity. Results indicate that these data sources are complementary. Community science contributes more observations, particularly of new species, in more locations and habitat types. Peer-reviewed papers and grey literature contribute more observations of conservative species and typically focus on protected areas. Even with 171,162 observations across these three data sources, there are still prominent data gaps. Differences in focus, protocol, and replication suggest it would be worthwhile to coordinate data acquisition across data sources, particularly focusing on collecting repeated observations to better understand factors impacting urban plant diversity and resilience.

Grasping at illusions: stimulating cutaneous afferents to create kinesthetic illusions - Jessica A. Leverett; John E. Misiaszek; Craig S. Chapman; David F. Collins (Experimental Brain Research, 2025)

Differential and Adjustable Stiffness Leaf Spring Ankle Foot Orthoses Enhance Gait Propulsion and Task Versatility in Cerebral Palsy - Collin D. Bowersock; Emmanuella A. Tagoe; Samuel Hopkins; Shanpu Fang; Zachary F. Lerner (Annals of Biomedical Engineering, 2025)

Noise from deep-sea mining in the Clarion-Clipperton Zone, Pacific Ocean will impact a broad range of marine taxa - Rob Williams; Kieran D. Cox; Diva Amon; Erin Ashe; Lucille Chapuis; Christine Erbe; Asha de Vos; Kimberly A. Nielsen; Marena Salerno Collins; Craig Smith; Travis Washburn; Kirsten F. Young; et al. (Marine Pollution Bulletin, 2025)

Small rainfall events increase belowground production in Chihuahuan Desert grassland - Scott L. Collins; Renée F. Brown (Ecology, 2025)
Dryland productivity is highly sensitive to precipitation variability, and models predict that rainfall variability will increase in the future. Numerous studies have documented the relationship between productivity and precipitation, but most focus on aboveground production (ANPP), while the effects on belowground production (BNPP) remain poorly understood. Furthermore, previous research suggests that ANPP and BNPP are uncoupled within ecosystems, but the degree to which rainfall variability affects the interplay between aboveground and belowground production is unknown. We conducted a long‐term rainfall manipulation experiment in Chihuahuan Desert grassland to investigate how the size and frequency of growing season rain events affected BNPP and its relationship to ANPP. Experimental plots received either 12 small‐frequent rain events or 3 large‐infrequent events during the monsoon season for a total of 60 mm of added rainfall per treatment per year. All plots, including three controls, received ambient rainfall throughout the year. Total BNPP ranged from a low of 94.7 ± 38.2 g m 2 year −1 under ambient conditions to a high of 183.7 ± 44.6 g m 2 year −1 under the small‐frequent rainfall treatment. Total BNPP was highest under small‐frequent rain events, and there was no difference in BNPP between 0–15 and 15–30 cm soil depths in either rainfall treatment. ANPP and BNPP were uncorrelated within rainfall treatments, but weakly positively correlated across all plots and years. Our results contribute to a growing body of research on the importance of small rain events in drylands and provide further evidence regarding the weak coupling between aboveground and belowground processes.

Precipitation‐productivity relationships in desert grassland: A test of the double asymmetry hypothesis - Scott L. Collins; Mariah T. Patton; Renée F. Brown (Ecology, 2025)
Understanding the relationship between precipitation (PPT) and aboveground net primary productivity (ANPP) is essential for modeling the global carbon cycle. Across grassland to forest gradients, the PPT‐ANPP relationship is well defined and nonlinear. Temporal patterns within a site over time are more variable and nearly always linear. Linear relationships, however, are inconsistent with positive asymmetry, where increases in ANPP during wet years exceed declines in dry years. The double asymmetry model predicts that concave‐down nonlinearities will occur when extreme high and low PPT years are included in a time series. We tested this prediction using long‐term observational ANPP data along with rainfall manipulation experiments. By combining observational records with experimental treatments, including drought, water addition, and nitrogen addition, we found some support for the double asymmetry model. However, the response under high precipitation coupled with nitrogen addition was concave‐up, not down. By experimentally extending the range of monsoon precipitation, we found a weak but significant, nonlinear PPT‐ANPP relationship, but only when nutrient limitation was alleviated. Our results demonstrate that multiple interacting factors govern the PPT‐ANPP relationship within a site over time, challenging our ability to predict how ANPP will respond to changes in precipitation in the future.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

Bioturbation and the resuspension of plastic pollutants by spawning common carp degrades lake water quality - Scott F. Collins (Science of The Total Environment, 2025)

Fitness incentives to male fighters undermine fighting performance in intergroup contests - P.A. Green; D.W.E. Sankey; T. Collins; F. Mwanguhya; H.J. Nichols; M.A. Cant; F.J. Thompson (Animal Behaviour, 2025)

10Be reproducibility in the Santa Monica Mountains, California, USA: A longitudinal study in a scorched and soaked landscape - Eric W. Portenga; Kirk F. Townsend; Lee B. Corbett; Paul R. Bierman; Marc W. Caffee; Collin Bogoski; Colin O'Neill; Samantha Skora (Geomorphology, 2025)

The plastic size spectra: Assessing the size structure of plastic particles across the land-water ecotone - Scott F. Collins; Andrea Norton (Environmental Pollution, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Self-report and actigraphy measures of sleep and domain-specific cognitive performance in older adults - Kelsey R. Sewell; Audrey M. Collins; Miranda G. Chappel-Farley; Shivangi Jain; Haiqing Huang; George Grove; Arthur F. Kramer; Edward McAuley; Jeffrey Burns; Charles Hillman; Eric Vidoni; Anna Marsland; et al. (GeroScience, 2025)

Evaluating the influence of high-resolution image capture on the signal strength of blue intensity and quantitative wood anatomy metrics from whitebark pine - Savannah A. Collins-Key; Maegen L. Rochner; Karen E. King; April L. Kaiser; Grant L. Harley; Zachary Foley; Matthew F. Bekker; Georg von Arx (Dendrochronologia, 2025)

Carbon footprints of greenhouse gas mitigation measures for a grass-based beef cattle finishing system in the UK - Asma Jebari; Taro Takahashi; Michael R. F. Lee; Adrian L. Collins; Kevin Coleman; Alison Carswell; Carmen Segura; Laura Cardenas; Graham A. McAuliffe (The International Journal of Life Cycle Assessment, 2025)
Purpose Agri-food systems across the globe are faced with the challenge of reducing their supply-chain emissions of greenhouse gases (GHGs) such as nitrous oxide (N 2 O), carbon dioxide (CO 2 ), and methane (CH 4 ). For instance, 10% of the UK’s GHG emissions are generated by agriculture, and ~ 56% of these are generated by livestock production. Numerous mitigation measures are being proposed to reduce GHG emissions from ruminants (representing 70 to 80% of total livestock emissions), particularly from beef cattle (presenting 30–40% of total livestock emissions). Methods To explore such potential, first, a business-as-usual (BAU) partial cradle-to-finishing farmgate scale modelling framework was developed. The BAU systems (i.e. steady-state productivity based on primary data from the North Wyke Farm Platform) were built using ensemble modelling wherein the RothC process-based soil organic carbon (SOC) model was integrated into the life cycle assessment (LCA) framework to conduct a trade-off analysis related to mitigation measures applicable to the study system. Potential mitigation measures were applied to the BAU scenario. The interventions assessed included: (i) extensification; (ii) adopting anaerobic digestion technology; and (iii) the use of the nitrification inhibitor DCD and substitution of fertiliser nitrogen with symbiotically fixed nitrogen from legumes. Results The partial carbon footprint for 1 kg of beef liveweight gain leaving the farmgate could be reduced by 7.5%, 12%, or 26% by adopting nitrification inhibitors, white clover introduction (pending establishment success), and anaerobic digestion for manure management, respectively. Conclusions The findings highlight the importance of including emissions beyond the farmgate level to analyse the carbon footprint of different management scenarios in order to assess the sustainability of agri-food production systems.

Unveiling hidden connections using photogrammetry: Multi-scale relationships between benthic communities and rocky subtidal seascapes - Q. Ternon; F. Ysnel; A. Collin; P. Thiriet; M. Guillaume; V. Danet; E. Feunteun (Regional Studies in Marine Science, 2025)

Enhanced crude oil degradation observed in sea ice following bioaugmentation with arctic bacteria - Diana Saltymakova; Durell S. Desmond; Alastair F. Smith; María A. Bautista; Eric Collins; Katarzyna Polcwiartek; Nolan Snyder; Teresinha Wolfe; Casey Hubert; Dustin Isleifson; Gary Stern (Marine Environmental Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Assessment of spatial variability and temporal stability of groundwater redox conditions in New Zealand - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne; Jon K. F. Roygard (Environmental Monitoring and Assessment, 2024)

A global systematic review of the cultural ecosystem services provided by wetlands - Kevin A. Wood; Lucy L. Jupe; Francisca C. Aguiar; Alexandra M. Collins; Scott J. Davidson; Will Freeman; Liam Kirkpatrick; Tatiana Lobato-de Magalhães; Emma McKinley; Ana Nuno; Jordi F. Pagès; Antonella Petruzzella; et al. (Ecosystem Services, 2024)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

A Latitudinal Cline in the Taxonomic Structure of Eelgrass Epifaunal Communities is Associated With Plant Genetic Diversity - Collin P. Gross; J. Emmett Duffy; Kevin A. Hovel; Pamela L. Reynolds; Christoffer Boström; Katharyn E. Boyer; Mathieu Cusson; Johan Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Global Ecology and Biogeography, 2024)
Aim Biogenic structural complexity increases mobile animal richness and abundance at local, regional and global scales, yet animal taxa vary in their response to complexity. When these taxa also vary functionally, habitat structures favouring certain taxa may have consequences for ecosystem function. We characterised global patterns of epifaunal invertebrates in eelgrass ( Zostera marina ) beds that varied in structural and genetic composition. Location North America, Europe and Asia. Time Period 2014. Major Taxa Studied Peracarid crustaceans and gastropod molluscs. Methods We sampled epifaunal invertebrate communities in 49 eelgrass beds across 37° latitude in two ocean basins concurrently with measurements of eelgrass genetic diversity, structural complexity and other abiotic and biotic environmental variables. We examined how species richness, abundance and community composition varied with latitude and environmental predictors using a random forest approach. We also examined how functional trait composition varied along with community structure. Results Total species richness decreased with latitude, but this was accompanied by a taxonomic shift in dominance from peracarid crustaceans to gastropods, which exhibited different sets of functional traits. Greater eelgrass genetic diversity was strongly correlated with both richness and abundance of peracarids, but less so for gastropods. Main Conclusions Our results add to a growing body of literature that suggests genetic variation in plant traits influences their associated faunal assemblages via habitat structure. Because peracarids and gastropods exhibited distinct functional traits, our results suggest a tentative indirect link between broad‐scale variation in plant genetic diversity and ecosystem function.

A review of lithogeochemical dispersion haloes of LCT pegmatites, and their application to rare metal exploration, with special reference to lithium in an Australian context - M. T. Sweetapple; P. J. Vanstone; G. R. Lumpkin; P. L. F. Collins (Australian Journal of Earth Sciences, 2024)

High-frequency spatial sediment source fingerprinting using in situ absorbance data - Niels F. Lake; Núria Martínez-Carreras; Peter J. Shaw; Adrian L. Collins (Journal of Hydrology, 2024)

Offshore windfarm construction elevates metabolic rate and increases predation vulnerability of a key marine invertebrate - Seth F. Cones; Youenn Jézéquel; Sierra Jarriel; Nadège Aoki; Hannah Brewer; John Collins; Laurent Chauvaud; T. Aran Mooney (Environmental Pollution, 2024)

Long-term trends in study duration of lakes and reservoirs over recent decades - T. M. Detmer; S. F. Collins; D. H. Wahl (Hydrobiologia, 2024)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

P06-18 Enhancing prediction and priorisation of adverse effects: TOXsIgN as a comprehensive resource for toxicogenomics - T. Darde; I. Kugathas; M. Boudet; A. Bretaudeau; R. Le Guével; L. Noël; T. Svingen; O. Collin; A. Rolland; F. Chalmel (Toxicology Letters, 2024)

Influence of the Keystone Grazer, Sesarma reticulatum, on the Hydrology and Organic Matter Cycling in Salt Marshes of the Southeastern USA - Elise S. Morrison; Thomas S. Bianchi; William F. Kenney; Mark Brenner; Kimberly Prince; Sydney Williams; Collin Ortals; Orlando Cordero; Sinéad M. Crotty; Christine Angelini (Estuaries and Coasts, 2024)
In salt marshes of the Southeastern USA, purple marsh crabs ( Sesarma reticulatum ), hereafter Sesarma , aggregate in grazing and burrowing fronts at the heads of tidal creeks, accelerating creek incision into marsh platforms. We explored the effects of this keystone grazer and sediment engineer on salt marsh sediment accumulation, hydrology, and carbon (C) and nitrogen (N) turnover using radionuclides ( 210 Pb and 7 Be), total hydrolyzable amino acids (THAA), and C and N stable isotopes (δ 13 C and δ 15 N) in sediment from paired Sesarma -grazed and un-grazed creeks. Sesarma -grazed-creek sediments exhibited greater bioturbation and tidal inundation compared to sediments in un-grazed creeks, as indicated by larger 210 Pb and 7 Be inventories. Total organic carbon (TOC) to total nitrogen (TN) weight ratios (C:N) were higher and δ 15 N values were lower in grazed-creek sediments than in un-grazed-creek sediments, suggesting Sesarma remove and assimilate N in their tissues, and excrete N with lower δ 15 N values into sediments. In support of this inference, the percent total carbon (TC) and percent TOC declined by nearly half, percent TN decreased by ~ 80%, and the C:N ratio exhibited a ~ threefold increase between Sesarma fore-gut and hind-gut contents. An estimated 91% of Sesarma ’s diet was derived from Spartina alterniflora, the region’s dominant salt marsh plant. We found that, as Sesarma grazing fronts progress across marsh landscapes, they enhance the decay of Spartina- derived organic matter and prolong marsh tidal inundation. These findings highlight the need to better account for the effects of keystone grazers and sediment engineers, like Sesarma , in estimates of the stability and size of blue C stores in coastal wetlands.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Biodiversity responses to Lateglacial climate change in the subdecadally-resolved record of Lake Hämelsee (Germany) - S. Engels; C.S. Lane; W.Z. Hoek; I. Baneschi; A. Bouwman; E. Brogan; C. Bronk Ramsey; J. Collins; R. de Bruijn; A. Haliuc; O. Heiri; K. Hubay; et al. (Quaternary Science Reviews, 2024)

Zircons reveal the history of fluctuations in oxidation state of crustal magmatism and supercontinent cycle - Rui Wang; Shao-chen Wu; Roberto F. Weinberg; William J. Collins; Peter A. Cawood (Science Bulletin, 2024)

Unburnt refugia support post-fire population recovery of a threatened arboreal marsupial, Leadbeater’s possum - Louise K. Durkin; Paul D. Moloney; Jemma K. Cripps; Jenny L. Nelson; Phoebe V. Macak; Michael P. Scroggie; Luke Collins; Luke D. Emerson; Jamie Molloy; Lindy F. Lumsden (Forest Ecology and Management, 2024)

The impact of a uniform ocean warming on the West African monsoon - Harry Mutton; Robin Chadwick; Matthew Collins; F. Hugo Lambert; Christopher M. Taylor; Ruth Geen; Alexander Todd (Climate Dynamics, 2024)
Projections of West African Monsoon (WAM) precipitation are uncertain. To address this, an improved understanding of the mechanisms driving WAM precipitation change is needed to shed light on inter-model differences and aid model development. The full forcing of increased CO 2 can be decomposed into different components such as the impact of ocean warming, or the direct radiative effect of increased CO 2 . This paper investigates such a decomposition, analysing the effect of a uniform 4K ocean warming whilst keeping atmospheric CO 2 concentrations constant. The analysis highlights several mechanisms acting to decrease WAM precipitation over a range of timescales, from days after the abrupt ocean warming, to the long-term equilibrium response. The initial decrease in WAM precipitation is caused by warming and enhanced convection over the ocean, stabilising the atmosphere inland and disrupting the monsoon inflow at low levels. Later in the response (after about 5 days), the WAM precipitation is reduced through a strengthening of the shallow circulation over West Africa, associated with changes in the large-scale temperature gradients and a local warming of the atmosphere related to a soil moisture feedback mechanism over the Sahel. Finally, from around 20 days after the SST increase, the WAM precipitation is also reduced through changes in specific humidity gradients that lead to increased potency of dry air advection into the monsoon rainband. The analysis concludes by demonstrating that the processes affecting precipitation in the early stages of the response are also relevant to the long-term equilibrium response.

Freshwater invertebrate responses to fine sediment stress: A multi‐continent perspective - Morwenna McKenzie; Andrew Brooks; Marcos Callisto; Adrian L. Collins; Jessica M. Durkota; Russell G. Death; J. Iwan Jones; Marden S. Linares; Christoph D. Matthaei; Wendy A. Monk; John F. Murphy; Annika Wagenhoff; et al. (Global Change Biology, 2024)
Excessive fine sediment (particles

Effects of a megafire vary with fire severity and forest type: The impact of Australia's ‘Black Summer’ fires on the superb lyrebird (Menura novaehollandiae), an iconic forest species - Alex C. Maisey; Luke Collins; Graeme Newell; Andrew F. Bennett (Biological Conservation, 2023)

Updated phylogeny of Vestimentifera (Siboglinidae, Polychaeta, Annelida) based on mitochondrial genomes, with a new species - Marina F. McCowin; Patrick C. Collins; Greg W. Rouse (Molecular Phylogenetics and Evolution, 2023)

The power of eDNA sampling to investigate the impact of Australian mega-fires on platypus occupancy - Emily F. McColl-Gausden; Josh Griffiths; Luke Collins; Andrew R. Weeks; Reid Tingley (Biological Conservation, 2023)

Understanding drivers of mercury in lake trout (Salvelinus namaycush), a top-predator fish in southwest Alaska's parklands - Krista K. Bartz; Michael P. Hannam; Tammy L. Wilson; Ryan F. Lepak; Jacob M. Ogorek; Daniel B. Young; Collin A. Eagles-Smith; David P. Krabbenhoft (Environmental Pollution, 2023)

Diet habits and trophic ecology of Rio Grande Sucker and Rio Grande Chub - Owen George; Scott F. Collins (Environmental Biology of Fishes, 2023)

As above, not so below: Long‐term dynamics of net primary production across a dryland transition zone - Renée F. Brown; Scott L. Collins (Global Change Biology, 2023)
Drylands are key contributors to interannual variation in the terrestrial carbon sink, which has been attributed primarily to broad‐scale climatic anomalies that disproportionately affect net primary production (NPP) in these ecosystems. Current knowledge around the patterns and controls of NPP is based largely on measurements of aboveground net primary production (ANPP), particularly in the context of altered precipitation regimes. Limited evidence suggests belowground net primary production (BNPP), a major input to the terrestrial carbon pool, may respond differently than ANPP to precipitation, as well as other drivers of environmental change, such as nitrogen deposition and fire. Yet long‐term measurements of BNPP are rare, contributing to uncertainty in carbon cycle assessments. Here, we used 16 years of annual NPP measurements to investigate responses of ANPP and BNPP to several environmental change drivers across a grassland–shrubland transition zone in the northern Chihuahuan Desert. ANPP was positively correlated with annual precipitation across this landscape; however, this relationship was weaker within sites. BNPP, on the other hand, was weakly correlated with precipitation only in Chihuahuan Desert shrubland. Although NPP generally exhibited similar trends among sites, temporal correlations between ANPP and BNPP within sites were weak. We found chronic nitrogen enrichment stimulated ANPP, whereas a one‐time prescribed burn reduced ANPP for nearly a decade. Surprisingly, BNPP was largely unaffected by these factors. Together, our results suggest that BNPP is driven by a different set of controls than ANPP. Furthermore, our findings imply belowground production cannot be inferred from aboveground measurements in dryland ecosystems. Improving understanding around the patterns and controls of dryland NPP at interannual to decadal scales is fundamentally important because of their measurable impact on the global carbon cycle. This study underscores the need for more long‐term measurements of BNPP to improve assessments of the terrestrial carbon sink, particularly in the context of ongoing environmental change.

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Use of a submersible spectrophotometer probe to fingerprint spatial suspended sediment sources at catchment scale - Niels F. Lake; Núria Martínez-Carreras; Jean François Iffly; Peter J. Shaw; Adrian L. Collins (Science of The Total Environment, 2023)

Environmental Impacts on Skin Microbiomes of Sympatric High Arctic Salmonids - Erin F. Hamilton; Collin L. Juurakko; Katja Engel; Josh D. Neufeld; John M. Casselman; Charles W. Greer; Virginia K. Walker (Fishes, 2023)
In the region of King William Island, Nunavut, in the Canadian high Arctic, populations of salmonids including Arctic char (Salvelinus alpinus), cisco (Coregonus autumnalis and C. sardinella) as well as lake whitefish (C. clupeaformis) are diadromous, overwintering in freshwater and transitioning to saline waters following ice melt. Since these fish were sampled at the same time and from the same traditional fishing sites, comparison of their skin structures, as revealed by 16S rRNA gene sequencing, has allowed an assessment of influences on wild fish bacterial communities. Arctic char skin microbiota underwent turnover in different seasonal habitats, but these striking differences in dispersion and diversity metrics, as well as prominent taxa involving primarily Proteobacteria and Firmicutes, were less apparent in the sympatric salmonids. Not only do these results refute the hypothesis that skin communities, for the most part, reflect water microbiota, but they also indicate that differential recruitment of bacteria is influenced by the host genome and physiology. In comparison to the well-adapted Arctic char, lake whitefish at the northern edge of their range may be particularly vulnerable, and we suggest the use of skin microbiomes as a supplemental tool to monitor a sustainable Indigenous salmonid harvest during this period of change in the high Arctic.

The biology of mammalian multi-copper ferroxidases - Sheridan L. Helman; Jie Zhou; Brie K. Fuqua; Yan Lu; James F. Collins; Huijun Chen; Christopher D. Vulpe; Gregory J. Anderson; David M. Frazer (BioMetals, 2023)

Protein quality as a complementary functional unit in life cycle assessment (LCA) - G. A. McAuliffe; T. Takahashi; T. Beal; T. Huppertz; F. Leroy; J. Buttriss; A. L. Collins; A. Drewnowski; S. J. McLaren; F. Ortenzi; J. C. van der Pols; S. van Vliet; et al. (The International Journal of Life Cycle Assessment, 2023)
Goal and theoretical commentary A number of recent life cycle assessment (LCA) studies have concluded that animal-sourced foods should be restricted—or even avoided—within the human diet due to their relatively high environmental impacts (particularly those from ruminants) compared with other protein-rich foods (mainly protein-rich plant foods). From a nutritional point of view, however, issues such as broad nutrient bioavailability, amino acid balances, digestibility and even non-protein nutrient density (e.g., micronutrients) need to be accounted for before making such recommendations to the global population. This is especially important given the contribution of animal sourced foods to nutrient adequacy in the global South and vulnerable populations of high-income countries (e.g., children, women of reproductive age and elderly). Often, however, LCAs simplify this reality by using ‘protein’ as a functional unit in their models and basing their analyses on generic nutritional requirements. Even if a ‘nutritional functional unit’ (nFU) is utilised, it is unlikely to consider the complexities of amino acid composition and subsequent protein accretion. The discussion herein focuses on nutritional LCA (nLCA), particularly on the usefulness of nFUs such as ‘protein,’ and whether protein quality should be considered when adopting the nutrient as an (n)FU. Further, a novel and informative case study is provided to demonstrate the strengths and weaknesses of protein-quality adjustment. Case study methods To complement current discussions, we present an exploratory virtual experiment to determine how Digestible Indispensable Amino Acid Scores (DIAAS) might play a role in nLCA development by correcting for amino acid quality and digestibility. DIAAS is a scoring mechanism which considers the limiting indispensable amino acids (IAAs) within an IAA balance of a given food (or meal) and provides a percentage contribution relative to recommended daily intakes for IAA and subsequent protein anabolism; for clarity, we focus only on single food items (4 × animal-based products and 4 × plant-based products) in the current case exemplar. Further, we take beef as a sensitivity analysis example (which we particularly recommend when considering IAA complementarity at the meal-level) to elucidate how various cuts of the same intermediary product could affect the interpretation of nLCA results of the end-product(s). Recommendations First, we provide a list of suggestions which are intended to (a) assist with deciding whether protein-quality correction is necessary for a specific research question and (b) acknowledge additional uncertainties by providing mitigating opportunities to avoid misinterpretation (or worse, dis-interpretation) of protein-focused nLCA studies. We conclude that as relevant (primary) data availability from supply chain ‘gatekeepers’ (e.g., international agri-food distributors and processors) becomes more prevalent, detailed consideration of IAA provision of contrasting protein sources needs to be acknowledged—ideally quantitatively with DIAAS being one example—in nLCA studies utilising protein as a nFU. We also contend that future nLCA studies should discuss the complementarity of amino acid balances at the meal-level, as a minimum, rather than the product level when assessing protein metabolic responses of consumers. Additionally, a broader set of nutrients should ideally be included when evaluating “protein-rich foods” which provide nutrients that extend beyond amino acids, which is of particular importance when exploring dietary-level nLCA.

A framework for detection and attribution of regional precipitation change: Application to the United States historical record - Mark D. Risser; William D. Collins; Michael F. Wehner; Travis A. O’Brien; Christopher J. Paciorek; John P. O’Brien; Christina M. Patricola-DiRosario; Huanping Huang; Paul A. Ullrich; Burlen Loring (Climate Dynamics, 2023)
Despite the emerging influence of anthropogenic climate change on the global water cycle, at regional scales the combination of observational uncertainty, large internal variability, and modeling uncertainty undermine robust statements regarding the human influence on precipitation. Here, we use output from global climate models in a perfect-data sense to develop a framework for conducting regional detection and attribution (D&A) for precipitation, starting with the contiguous United States (CONUS) where observational uncertainty is lower than in other regions. Our unified approach can simultaneously detect systematic trends in mean and extreme precipitation, attribute trends to anthropogenic forcings, compute the effects of forcings as a function of time, and map the effects of individual forcings. Model output is used to conduct a set of tests that yield a parsimonious representation for characterizing seasonal precipitation over the CONUS for the historical record (1900 to present day), which ensures our D&A is insensitive to structural uncertainty. Our framework is developed using synthetic data in a Pearl-causal perspective wherein causality can be identified using intervention-based simulations. While the hypothesis-based framework and accompanying generalized D&A formula we develop should be widely applicable, we include a strong caution that the hypothesis-guided simplification of the formula for the historical climatic record of CONUS as described in this paper will likely fail to hold in other geographic regions and under future warming.

Warmer and drier conditions have increased the potential for large and severe fire seasons across south‐eastern Australia - Luke Collins; Hamish Clarke; Michael F. Clarke; Sarah C. McColl Gausden; Rachael H. Nolan; Trent Penman; Ross Bradstock (Global Ecology and Biogeography, 2022)
Aim The aims were: (1) to identify the environmental drivers of interannual variation in wildfire extent and severity; (2) to examine temporal trends in climatic potential for large and severe wildfires; and (3) to assess whether environmental conditions experienced during the 2019–2020 mega‐fire season were anomalous. Location South‐eastern Australia. Time period 1953–2020. Major taxa studied Temperate forests. Methods We used satellite‐derived fire severity mapping from 1988 to 2020 to model the effects of drought, weather and fuels on the annual area burned and the proportion of the area burned that was impacted by high‐severity fire across four bioregions. Trends in wildfire extent and severity were then estimated from 1953 to 2020 using these derived models and gridded climate data to assess changes in climatic potential for large and severe wildfires. Estimates of wildfire extent and severity for the 2019–2020 fire season were then assessed against prior seasons (1953–2019). Results Annual area burned was positively related to the severity of seasonal drought and frequency of fire weather conditions that promote substantial daily fire growth. Wildfire severity was elevated in years with severe fire weather and increased with increasing antecedent drought in years without severe fire weather. Fuels had a lesser effect on wildfire extent and severity than climate. Potential fire extent and severity have increased over time in response to an increased severity of drought and worsening fire weather conditions. Estimates of wildfire extent and severity during the 2019–2020 fire season approached the upper extreme within each bioregion, owing to widespread extreme climatic conditions. Main conclusions The climatic potential for large and severe forest fires has increased across south‐eastern Australia since the 1950s, probably because of anthropogenic climate change. The magnitude and severity of the 2019–2020 fires reflected climatic conditions that are driving an increase in the size and severity of wildfires.

The carbon cost of the 2019–20 Australian fires varies with fire severity and forest type - Rachael H. Nolan; Luke Collins; Rebecca K. Gibson; Stephanie A. Samson; Katherine T. Rolls; Kirsty Milner; Belinda E. Medlyn; Owen F. Price; Anne Griebel; Brendan Choat; Mingkai Jiang; Matthias M. Boer (Global Ecology and Biogeography, 2022)
Aim To estimate loss of above‐ground carbon (AGC) and conversion of live carbon to dead carbon following understorey and canopy fire. Location South‐eastern Australia. Time period 2019–2020. Major taxa studied Four widespread resprouting eucalypt forests. Methods Above‐ground carbon was measured in 15 plots in each of four forest types one‐year post‐fire. We also assessed topkill, that is, trees subject to canopy loss that failed to resprout epicormically. Results While canopy fire was associated with greater declines in AGC than understorey fire, this was only statistically significant for only one forest type, where AGC declined from 154 to 85 Mg C ha −1 following canopy fire. Significant post‐fire increases in dead AGC were observed in one forest type, where dead carbon increased from 22 to 60% after canopy fire. Topkill of trees following canopy fire (48–78% of stems) was higher than topkill after understorey fire (36–53% of stems) and in unburnt forest (12–55%). Topkill occurred primarily in small‐diameter stems. Consequently, there was no effect of fire on the proportion of dead AGC in trees, with the exception of the forest with lowest productivity (i.e., lowest biomass) and lowest annual rainfall, where dead tree carbon increased from 8% in unburnt forest to 13 and 53% after understorey and canopy fire, respectively. AGC in understorey vegetation and coarse woody debris was similar or lower in burnt compared with unburnt forest. Litter carbon was significantly lower and pyrogenic carbon significantly higher in burnt forest, with no difference between understorey and canopy fire. Main conclusions While increased fire severity was associated with increased changes to carbon stocks, there were differences among forest types. Specifically, the driest forest type had the highest rates of topkill following canopy fire. These results highlight the importance of spatial variability in fire severity and forest type in determining the effects of fire on carbon stocks.

Frozen in time: Rangewide genomic diversity, structure, and demographic history of relict American chestnut populations - Alexander M. Sandercock; Jared W. Westbrook; Qian Zhang; Hayley A. Johnson; Thomas M. Saielli; John A. Scrivani; Sara F. Fitzsimmons; Kendra Collins; Matthew Taylor Perkins; James Hill Craddock; Jeremy Schmutz; Jane Grimwood; et al. (Molecular Ecology, 2022)
American chestnut ( Castanea dentata ) was once the most economically and ecologically important hardwood species in the eastern United States. In the first half of the 20th century, an exotic fungal pathogen— Cryphonectria parasitica —decimated the species, killing billions of chestnut trees. Two approaches to developing blight‐resistant American chestnut populations show promise, but both will require introduction of adaptive genomic diversity from wild germplasm to produce diverse, locally adapted restoration populations. Here we characterize population structure, demographic history, and genomic diversity in a range‐wide sample of 384 wild American chestnuts to inform conservation and breeding with blight‐resistant varieties. Population structure analyses suggest that the chestnut range can be roughly divided into northeast, central, and southwest populations. Within‐population genomic diversity estimates revealed a clinal pattern with the highest diversity in the southwest, which likely reflects bottleneck events associated with Quaternary glaciation. Finally, we identified genomic regions under positive selection within each population, which suggests that defence against fungal pathogens is a common target of selection across all populations. Taken together, these results show that American chestnut underwent a postglacial expansion from the southern portion of its range leading to three extant genetic populations. These populations will serve as management units for breeding adaptive genetic variation into the blight‐resistant tree populations for targeted reintroduction efforts.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Using structured decision making to guide habitat restoration for butterflies: a case study of Oregon silverspots - Cassandra F. Doll; Sarah J. Converse; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2022)

High frequency un-mixing of soil samples using a submerged spectrophotometer in a laboratory setting—implications for sediment fingerprinting - Niels F. Lake; Núria Martínez-Carreras; Peter J. Shaw; Adrian L. Collins (Journal of Soils and Sediments, 2022)
Purpose This study tests the feasibility of using a submersible spectrophotometer as a novel method to trace and apportion suspended sediment sources in situ and at high temporal frequency. Methods Laboratory experiments were designed to identify how absorbance at different wavelengths can be used to un-mix artificial mixtures of soil samples (i.e. sediment sources). The experiment consists of a tank containing 40 L of water, to which the soil samples and soil mixtures of known proportions were added in suspension. Absorbance measurements made using the submersible spectrophotometer were used to elucidate: (i) the effects of concentrations on absorbance, (ii) the relationship between absorbance and particle size and (iii) the linear additivity of absorbance as a prerequisite for un-mixing. Results The observed relationships between soil sample concentrations and absorbance in the ultraviolet visible (UV–VIS) wavelength range (200–730 nm) indicated that differences in absorbance patterns are caused by soil-specific properties and particle size. Absorbance was found to be linearly additive and could be used to predict the known soil sample proportions in mixtures using the MixSIAR Bayesian tracer mixing model. Model results indicate that dominant contributions to mixtures containing two and three soil samples could be predicted well, whilst accuracy for four-soil sample mixtures was lower (with respective mean absolute errors of 15.4%, 12.9% and 17.0%). Conclusion The results demonstrate the potential for using in situ submersible spectrophotometer sensors to trace suspended sediment sources at high temporal frequency.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Does increasing the number of channels during neuromuscular electrical stimulation reduce fatigability and produce larger contractions with less discomfort? - Trevor S. Barss; Bailey W. M. Sallis; Dylan J. Miller; David F. Collins (European Journal of Applied Physiology, 2021)

First Insight of Meso- and Bentho-Pelagic Fish Dynamics Around Remote Seamounts in the South Atlantic Ocean - Fabio Campanella; Martin A. Collins; Emma F. Young; Vladimir Laptikhovsky; Paul Whomersley; Jeroen van der Kooij (Frontiers in Marine Science, 2021)
Seamounts have long been recognised as hotspots for pelagic productivity and diversity in the world’s open ocean habitats. Recent studies have suggested that productivity may vary greatly between different seamounts, depending on complex interactions between the bathymetric features and local oceanography. These processes may enhance local primary production which support elevated biomass at higher trophic levels. In addition to enhancing local biomass, seamounts may also act as aggregative features, attracting pelagic species from the surrounding waters. Such characteristics make seamounts attractive targets for fisheries. However, as these unique habitats are localised and relatively small, they are vulnerable to overexploitation, which may have detrimental impact on the wider region. Mapping and quantitative assessments of the fish biomass at different seamounts are crucial prerequisites to identifying vulnerable seamounts and will aid toward understanding the dynamics of these important ecosystems and their vulnerability to fishing pressures. We used fisheries acoustics during two expeditions in 2018 and 2019, to investigate the distribution and abundance of fish and micronekton on and around five little studied seamounts of Tristan da Cunha, a remote archipelago in the South Atlantic Ocean. The results confirmed increased productivity at the seamounts, compared to the surrounding open ocean with higher acoustic backscatter values, a proxy for biomass, particularly at the shallower (~200 m depth) seamounts. Fish largely dominated the backscatter on most of the seamounts especially over the plateau areas where large densities of prey fish, primarily the mesopelagic Maurolicus inventionis , were detected. Very large aggregations, thought to consist of bentho-pelagic fish, were also observed over the slope of McNish Seamount that resulted in very high biomass estimates. Aggregations of this size and magnitude, have, to our knowledge, never been mapped or quantified on seamounts, using acoustic methods. Specific physical processes, such as enhanced retention and vertical mixing that were identified by an oceanographic model, may be some of the drivers of the enhanced fish biomass detected at McNish. The characteristics of the seamounts observed in this work suggest that these habitats are highly suitable for the presence of large predatory fish that can utilise these areas as their primary habitat or as important foraging grounds.

Quantifying the influence of natural climate variability on in situ measurements of seasonal total and extreme daily precipitation - Mark D. Risser; Michael F. Wehner; John P. O’Brien; Christina M. Patricola-DiRosario; Travis A. O’Brien; William D. Collins; Christopher J. Paciorek; Huanping Huang (Climate Dynamics, 2021)
While various studies explore the relationship between individual sources of climate variability and extreme precipitation, there is a need for improved understanding of how these physical phenomena simultaneously influence precipitation in the observational record across the contiguous United States. In this work, we introduce a single framework for characterizing the historical signal (anthropogenic forcing) and noise (natural variability) in seasonal mean and extreme precipitation. An important aspect of our analysis is that we simultaneously isolate the individual effects of seven modes of variability while explicitly controlling for joint inter-mode relationships. Our method utilizes a spatial statistical component that uses in situ measurements to resolve relationships to their native scales; furthermore, we use a data-driven procedure to robustly determine statistical significance. In Part I of this work we focus on natural climate variability: detection is mostly limited to DJF and SON for the modes of variability considered, with the El Niño/Southern Oscillation, the Pacific–North American pattern, and the North Atlantic Oscillation exhibiting the largest influence. Across all climate indices considered, the signals are larger and can be detected more clearly for seasonal total versus extreme precipitation. We are able to detect at least some significant relationships in all seasons in spite of extremely large (> 95%) background variability in both mean and extreme precipitation. Furthermore, we specifically quantify how the spatial aspect of our analysis reduces uncertainty and increases detection of statistical significance while also discovering results that quantify the complex interconnected relationships between climate drivers and seasonal precipitation.

Effects of Chlorpyrifos Over Reproductive Traits of Three Sympatric Freshwater Crustaceans - C. L. Negro; J. F. Estrubia; F. Rivera; P. Collins (Bulletin of Environmental Contamination and Toxicology, 2021)

Negative impacts of invasive predators used as biological control agents against the pest snail Lissachatina fulica: the snail Euglandina ‘rosea’ and the flatworm Platydemus manokwari - Justin Gerlach; Gary M. Barker; Cindy S. Bick; Philippe Bouchet; Gilianne Brodie; Carl C. Christensen; Timothy Collins; Trevor Coote; Robert H. Cowie; G. Curt Fiedler; Owen L. Griffiths; F. B. Vincent Florens; et al. (Biological Invasions, 2021)
Since 1955 snails of the Euglandina rosea species complex and Platydemus manokwari flatworms were widely introduced in attempted biological control of giant African snails ( Lissachatina fulica ) but have been implicated in the mass extinction of Pacific island snails. We review the histories of the 60 introductions and their impacts on L. fulica and native snails. Since 1993 there have been unofficial releases of Euglandina within island groups. Only three official P. manokwari releases took place, but new populations are being recorded at an increasing rate, probably because of accidental introduction. Claims that these predators controlled L. fulica cannot be substantiated; in some cases pest snail declines coincided with predator arrival but concomitant declines occurred elsewhere in the absence of the predator and the declines in some cases were only temporary. In the Hawaiian Islands, although there had been some earlier declines of native snails, the Euglandina impacts on native snails are clear with rapid decline of many endemic Hawaiian Achatinellinae following predator arrival. In the Society Islands, Partulidae tree snail populations remained stable until Euglandina introduction, when declines were extremely rapid with an exact correspondence between predator arrival and tree snail decline. Platydemus manokwari invasion coincides with native snail declines on some islands, notably the Ogasawara Islands of Japan, and its invasion of Florida has led to mass mortality of Liguus spp. tree snails. We conclude that Euglandina and P. manokwari are not effective biocontrol agents, but do have major negative effects on native snail faunas. These predatory snails and flatworms are generalist predators and as such are not suitable for biological control.

Holistic Assessment of Biochar and Brown Coal Waste as Organic Amendments in Sustainable Environmental and Agricultural Applications - Collins Amoah-Antwi; Jolanta Kwiatkowska-Malina; Owen Fenton; Ewa Szara; Steven F. Thornton; Grzegorz Malina (Water, Air, & Soil Pollution, 2021)
Organic amendments can improve soil quality which has knock-on environmental and agronomic benefits. However, the use of new and emerging organic amendments such as biochar and brown coal waste (BCW) in soil systems requires continuous holistic assessments for robust consensus building in their environmental and agricultural applications. To examine the application of BCW and woodchip biochar (BIO) in agroecosystems, secondary data from literature on environmental (soil, air and water) aspects were compiled with primary agronomic data from a 3-year multicropping field trial and collated with supplementary data on economic factors (e.g. cost and availability). For the field trial, replicated plots were amended with FYM (for comparative reasons), BCW and BIO at 30, 24.2 and 12.8 for t ha –1 , respectively, with and without NPK and cultivated in a cropping sequence of maize, potato and barley. At the end of each season, soils were characterised for pH, cation exchange capacity (CEC) and fertility (macronutrient contents) in addition to nutrient uptake, nutritional quality and yield of crops. Compared with FYM, biochar and BCW were found to be associated with greater improvements in soil quality (e.g. building of soil structure and C sequestration) and knock-on water and air quality benefits mainly facilitated via increased cation retention and humic-linked sorption which abated gaseous emission and mitigated nutrient and heavy metal leaching. These along with variable improvements in soil chemistry, fertility and nutrient uptake in the agronomic field trial accounted for increased mean crop yield across treatments (higher with NPK): FYM (32.7 and 71.7%), BCW (33.5 and 60.1%) and BIO (21.8 and 48.2%). Additionally, biochar and BCW have lower pollutant (e.g. heavy metals) contents and were found to provide additional sustainability and net abatement cost-benefits. While the agronomic benefits of biochar and BCW were slightly lower compared with that of FYM, their lower environmental footprints and associated sustainability benefits are clear advantages for their adoption in environmental and agricultural applications.

Whole Community Metatranscriptomes and Lipidomes Reveal Diverse Responses Among Antarctic Phytoplankton to Changing Ice Conditions - Jeff S. Bowman; Benjamin A. S. Van Mooy; Daniel P. Lowenstein; Helen F. Fredricks; Colleen M. Hansel; Rebecca Gast; James R. Collins; Nicole Couto; Hugh W. Ducklow (Frontiers in Marine Science, 2021)
The transition from winter to spring represents a major shift in the basal energy source for the Antarctic marine ecosystem from lipids and other sources of stored energy to sunlight. Because sea ice imposes a strong control on the transmission of sunlight into the water column during the polar spring, we hypothesized that the timing of the sea ice retreat influences the timing of the transition from stored energy to photosynthesis. To test the influence of sea ice on water column microbial energy utilization we took advantage of unique sea ice conditions in Arthur Harbor, an embayment near Palmer Station on the western Antarctic Peninsula, during the 2015 spring–summer seasonal transition. Over a 5-week period we sampled water from below land-fast sea ice, in the marginal ice zone at nearby Palmer Station B, and conducted an ice removal experiment with incubations of water collected below the land-fast ice. Whole-community metatranscriptomes were paired with lipidomics to better understand how lipid production and utilization was influenced by light conditions. We identified several different phytoplankton taxa that responded similarly to light by the number of genes up-regulated, and in the transcriptional complexity of this response. We applied a principal components analysis to these data to reduce their dimensionality, revealing that each of these taxa exhibited a strikingly different pattern of gene up-regulation. By correlating the changes in lipid concentration to the first principal component of log fold-change for each taxa we could make predictions about which taxa were associated with different changes in the community lipidome. We found that genes coding for the catabolism of triacylglycerol storage lipids were expressed early on in phytoplankton associated with a Fragilariopsis kerguelensis reference transcriptome. Phytoplankton associated with a Corethron pennatum reference transcriptome occupied an adjacent niche, responding favorably to higher light conditions than F. kerguelensis . Other diatom and dinoflagellate taxa had distinct transcriptional profiles and correlations to lipids, suggesting diverse ecological strategies during the polar winter–spring transition.

Gene expression during larval caste determination and differentiation in intermediately eusocial bumblebees, and a comparative analysis with advanced eusocial honeybees - David H. Collins; Anders Wirén; Marjorie Labédan; Michael Smith; David C. Prince; Irina Mohorianu; Tamas Dalmay; Andrew F. G. Bourke (Molecular Ecology, 2021)
The queen‐worker caste system of eusocial insects represents a prime example of developmental polyphenism (environmentally‐induced phenotypic polymorphism) and is intrinsic to the evolution of advanced eusociality. However, the comparative molecular basis of larval caste determination and subsequent differentiation in the eusocial Hymenoptera remains poorly known. To address this issue within bees, we profiled caste‐associated gene expression in female larvae of the intermediately eusocial bumblebee Bombus terrestris . In B . terrestris , female larvae experience a queen‐dependent period during which their caste fate as adults is determined followed by a nutrition‐sensitive period also potentially affecting caste fate but for which the evidence is weaker. We used mRNA‐seq and qRT‐PCR validation to isolate genes differentially expressed between each caste pathway in larvae at developmental stages before and after each of these periods. We show that differences in gene expression between caste pathways are small in totipotent larvae, then peak after the queen‐dependent period. Relatively few novel (i.e., taxonomically‐restricted) genes were differentially expressed between castes, though novel genes were significantly enriched in late‐instar larvae in the worker pathway. We compared sets of caste‐associated genes in B . terrestris with those reported from the advanced eusocial honeybee, Apis mellifera , and found significant but relatively low levels of overlap of gene lists between the two species. These results suggest both the existence of low numbers of shared toolkit genes and substantial divergence in caste‐associated genes between Bombus and the advanced eusocial Apis since their last common eusocial ancestor.

Forest Vegetation Change and Its Impacts on Soil Water Following 47 Years of Managed Wildfire - Jens T. Stevens; Gabrielle F. S. Boisramé; Ekaterina Rakhmatulina; Sally E. Thompson; Brandon M. Collins; Scott L. Stephens (Ecosystems, 2020)

The indigoidine synthetase BpsA provides a colorimetric ATP assay that can be adapted to quantify the substrate preferences of other NRPS enzymes - Alistair S. Brown; Mark J. Calcott; Vincent M. Collins; Jeremy G. Owen; David F. Ackerley (Biotechnology Letters, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Ferric-Induced Pancreatic Injury Involves Exacerbation of Cholinergic and Proteolytic Activities, and Dysregulation of Metabolic Pathways: Protective Effect of Caffeic Acid - Veronica F. Salau; Ochuko L. Erukainure; Collins U. Ibeji; Neil A. Koorbanally; Md. Shahidul Islam (Biological Trace Element Research, 2020)

Efficacy of VERYL® in the treatment of cattle naturally infected with gastro-intestinal nematodes in Kenya - M. W. Maichomo; J. M. Nginyi; A. Caruso-Varès; E. O. Mungube; G. Pagny; C. Chevtzoff; J. C. Njanja; P. A. Lumumba; J. F. Collin; N. Isaka (Tropical Animal Health and Production, 2020)

Vanillin and vanillic acid modulate antioxidant defense system via amelioration of metabolic complications linked to Fe2+-induced brain tissues damage - Veronica F. Salau; Ochuko L. Erukainure; Collins U. Ibeji; Tosin A. Olasehinde; Neil A. Koorbanally; Md. Shahidul Islam (Metabolic Brain Disease, 2020)

Ferulic Acid Modulates Dysfunctional Metabolic Pathways and Purinergic Activities, While Stalling Redox Imbalance and Cholinergic Activities in Oxidative Brain Injury - Veronica F. Salau; Ochuko L. Erukainure; Collins U. Ibeji; Tosin A. Olasehinde; Neil A. Koorbanally; Md. Shahidul Islam (Neurotoxicity Research, 2020)

Sensitivity of primary production to precipitation across the United States - Gregory E. Maurer; Alesia J. Hallmark; Renée F. Brown; Osvaldo E. Sala; Scott L. Collins (Ecology Letters, 2020)
Primary production, a key regulator of the global carbon cycle, is highly responsive to variations in climate. Yet, a detailed, continental‐scale risk assessment of climate‐related impacts on primary production is lacking. We combined 16 years of MODIS NDVI data, a remotely sensed proxy for primary production, with observations from 1218 climate stations to derive values of ecosystem sensitivity to precipitation and aridity. For the first time, we produced an empirically‐derived map of ecosystem sensitivity to climate across the conterminous United States. Over this 16‐year period, annual primary production values were most sensitive to precipitation and aridity in dryland and grassland ecosystems. Century‐long trends measured at the climate stations showed intensifying aridity and climatic variability in many of these sensitive regions. Dryland ecosystems in the western US may be particularly vulnerable to reductions in primary production and consequent degradation of ecosystem services as climate change and variability increase in the future.

Reverberating effects of resource exchanges in stream–riparian food webs - Scott F. Collins; Colden V. Baxter; Amy M. Marcarelli; Laura Felicetti; Scott Florin; Mark S. Wipfli; Gregg Servheen (Oecologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

New insights into Neolithic milk consumption through proteomic analysis of dental calculus - Sophy Charlton; Abigail Ramsøe; Matthew Collins; Oliver E. Craig; Roman Fischer; Michelle Alexander; Camilla F. Speller (Archaeological and Anthropological Sciences, 2019)
There has long been debate over the origins of dairy consumption within European populations. Whilst it was previously assumed that lactase persistence (LP) was under positive selection following the advent of agriculture, recent genetic studies of prehistoric human remains have revealed LP may have only emerged in Europe in the last 4000 years. These findings stand in contrast to organic residue analysis of Neolithic pottery indicating the utilisation of dairy products, and zooarchaeological mortality profiles consistent with dairying herds at Neolithic sites. The recent discovery of the milk protein β-lactoglobulin (BLG) within human dental calculus presents a new method via which to explore dairy product consumption in the archaeological past. Here, we apply shotgun proteomic analysis to dental calculus samples from three British Neolithic sites, revealing the earliest identification of BLG in human dental calculus to date. The presence of BLG peptides in individuals who are unlikely to possess LP provides new insight into dairying in the British Neolithic, suggesting the potential processing of milk by Neolithic populations to reduce the lactose content of dairy products.

Wildfire refugia in forests: Severe fire weather and drought mute the influence of topography and fuel age - Luke Collins; Andrew F. Bennett; Steve W. J. Leonard; Trent D. Penman (Global Change Biology, 2019)
Wildfire refugia (unburnt patches within large wildfires) are important for the persistence of fire‐sensitive species across forested landscapes globally. A key challenge is to identify the factors that determine the distribution of fire refugia across space and time. In particular, determining the relative influence of climatic and landscape factors is important in order to understand likely changes in the distribution of wildfire refugia under future climates. Here, we examine the relative effect of weather (i.e. fire weather, drought severity) and landscape features (i.e. topography, fuel age, vegetation type) on the occurrence of fire refugia across 26 large wildfires in south‐eastern Australia. Fire weather and drought severity were the primary drivers of the occurrence of fire refugia, moderating the effect of landscape attributes. Unburnt patches rarely occurred under ‘severe’ fire weather, irrespective of drought severity, topography, fuels or vegetation community. The influence of drought severity and landscape factors played out most strongly under ‘moderate’ fire weather. In mesic forests, fire refugia were linked to variables that affect fuel moisture, whereby the occurrence of unburnt patches decreased with increasing drought conditions and were associated with more mesic topographic locations (i.e. gullies, pole‐facing aspects) and vegetation communities (i.e. closed‐forest). In dry forest, the occurrence of refugia was responsive to fuel age, being associated with recently burnt areas (

A direct comparison of divalent metal-ion transporter (DMT1) and hinokitiol, a potential small molecule replacement - Michael D. Garrick; Laura M. Garrick; Lin Zhao; James F. Collins; Joleen Soukup; Andrew J. Ghio (BioMetals, 2019)

Solution structure and biochemical characterization of a spare part protein that restores activity to an oxygen-damaged glycyl radical enzyme - Sarah E. J. Bowman; Lindsey R. F. Backman; Rebekah E. Bjork; Mary C. Andorfer; Santiago Yori; Alessio Caruso; Collin M. Stultz; Catherine L. Drennan (JBIC Journal of Biological Inorganic Chemistry, 2019)

A probabilistic gridded product for daily precipitation extremes over the United States - Mark D. Risser; Christopher J. Paciorek; Michael F. Wehner; Travis A. O’Brien; William D. Collins (Climate Dynamics, 2019)

Are Oxidative Stress Biomarkers Sensitive to Environmental Concentrations of Chlorpyrifos Exposed to the Freshwater Crab, Zilchiopsis collastinensis (Decapoda; Trichodactylidae)? - C. L. Negro; F. G. Iturburu; J. Mendieta; M. L. Menone; P. Collins (Bulletin of Environmental Contamination and Toxicology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Comparison of microscopy to a semi-automated method (FlowCAM®) for characterization of individual-, population-, and community-level measurements of zooplankton - Thomas M. Detmer; Kyle J. Broadway; Cal G. Potter; Scott F. Collins; Joseph J. Parkos; David H. Wahl (Hydrobiologia, 2019)

Avian host composition, local speciation and dispersal drive the regional assembly of avian malaria parasites in South American birds - Alan Fecchio; Jeffrey A. Bell; Rafael B.P. Pinheiro; Victor R. Cueto; Cristian A. Gorosito; Holly L. Lutz; Milene G. Gaiotti; Luciana V. Paiva; Leonardo F. França; Guilherme Toledo‐Lima; Mariana Tolentino; João B. Pinho; et al. (Molecular Ecology, 2019)
Identifying the ecological factors that shape parasite distributions remains a central goal in disease ecology. These factors include dispersal capability, environmental filters and geographic distance. Using 520 haemosporidian parasite genetic lineages recovered from 7,534 birds sampled across tropical and temperate South America, we tested (a) the latitudinal diversity gradient hypothesis and (b) the distance–decay relationship (decreasing proportion of shared species between communities with increasing geographic distance) for this host–parasite system. We then inferred the biogeographic processes influencing the diversity and distributions of this cosmopolitan group of parasites across South America. We found support for a latitudinal gradient in diversity for avian haemosporidian parasites, potentially mediated through higher avian host diversity towards the equator. Parasite similarity was correlated with climate similarity, geographic distance and host composition. Local diversification in Amazonian lineages followed by dispersal was the most frequent biogeographic events reconstructed for haemosporidian parasites. Combining macroecological patterns and biogeographic processes, our study reveals that haemosporidian parasites are capable of circumventing geographic barriers and dispersing across biomes, although constrained by environmental filtering. The contemporary diversity and distributions of haemosporidian parasites are mainly driven by historical (speciation) and ecological (dispersal) processes, whereas the parasite community assembly is largely governed by host composition and to a lesser extent by environmental conditions.

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Different loci associated with root and foliar resistance to sudden death syndrome (Fusarium virguliforme) in soybean - Ruijuan Tan; Paul J. Collins; Jie Wang; Zixiang Wen; John F. Boyse; Randall G. Laurenz; Cuihua Gu; Janette L. Jacobs; Qijian Song; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2019)

Acquisition of obligate mutualist symbionts during the larval stage is not beneficial for a coral host - Aaron C. Hartmann; Kristen L. Marhaver; Anke Klueter; Michael T. Lovci; Collin J. Closek; Erika Diaz; Valérie F. Chamberland; Frederick I. Archer; Dimitri D. Deheyn; Mark J. A. Vermeij; Mónica Medina (Molecular Ecology, 2019)
Theory suggests that the direct transmission of beneficial endosymbionts (mutualists) from parents to offspring (vertical transmission) in animal hosts is advantageous and evolutionarily stable, yet many host species instead acquire their symbionts from the environment (horizontal acquisition). An outstanding question in marine biology is why some scleractinian corals do not provision their eggs and larvae with the endosymbiotic dinoflagellates that are necessary for a juvenile's ultimate survival. We tested whether the acquisition of photosynthetic endosymbionts (family Symbiodiniaceae) during the planktonic larval stage was advantageous, as is widely assumed, in the ecologically important and threatened Caribbean reef‐building coral Orbicella faveolata . Following larval acquisition, similar changes occurred in host energetic lipid use and gene expression regardless of whether their symbionts were photosynthesizing, suggesting the symbionts did not provide the energetic benefit characteristic of the mutualism in adults. Larvae that acquired photosymbionts isolated from conspecific adults on their natal reef exhibited a reduction in swimming, which may interfere with their ability to find suitable settlement substrate, and also a decrease in survival. Larvae exposed to two cultured algal species did not exhibit differences in survival, but decreased their swimming activity in response to one species. We conclude that acquiring photosymbionts during the larval stage confers no advantages and can in fact be disadvantageous to this coral host. The timing of symbiont acquisition appears to be a critical component of a host's life history strategy and overall reproductive fitness, and this timing itself appears to be under selective pressure.

QTL mapping and epistatic interaction analysis of field resistance to sudden death syndrome (Fusarium virguliforme) in soybean - Ruijuan Tan; Bradley Serven; Paul J. Collins; Zhongnan Zhang; Zixiang Wen; John F. Boyse; Cuihua Gu; Martin I. Chilvers; Brian W. Diers; Dechun Wang (Theoretical and Applied Genetics, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Habitat disruption and the identification and management of functional trait changes - Jennifer L Kelley; Pauline F Grierson; Shaun P Collin; Peter M Davies (Fish and Fisheries, 2018)
Aquatic ecosystems are facing escalating threats from urbanization, habitat loss and projected impacts of climate change, which both individually and in combination have the potential to fundamentally alter ecosystem functioning. While it is well established that habitat disturbances can affect the composition and diversity of aquatic communities, only recently have studies considered whether such impacts result in changes in species’ functional traits. We consider how functional traits of freshwater and marine fishes respond to environmental change, and how shifts in the expression of these traits can impact community dynamics and key ecological processes, including trophic interactions and nutrient transfer. We find that a multitude of functional traits, including behavioural and sensory traits, is sensitive to habitat disturbances. We demonstrate how these trait changes can be used to reveal hidden “ecological diversity” as well as serving as early indicators of environmental perturbation. We conclude that management strategies that consider the fundamental biological responses of fishes to habitat disturbance will be particularly effective in determining causal relationships within the ecological network. While detailed information on trait function is often lacking, even some general understanding of trait function and importance will facilitate targeted and efficient ecosystem management. We urge fisheries biologists and aquatic ecosystem managers to consider the role of functional traits in facilitating effective habitat restoration and management.

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

The release and regulation of rotifers: examining the predatory effects of invasive juvenile common and bighead carp - Scott F. Collins; Thomas M. Detmer; Kirsten A. Nelson; Michael A. Nannini; Greg G. Sass; David H. Wahl (Hydrobiologia, 2018)

Route of Feeding as a Proxy for Dysphagia After Stroke and the Effect of Transdermal Glyceryl Trinitrate: Data from the Efficacy of Nitric Oxide in Stroke Randomised Controlled Trial - Lisa J Woodhouse; Polly Scutt; Shaheen Hamdy; David G Smithard; David L Cohen; Christine Roffe; Daniel Bereczki; Eivind Berge; Christopher F Bladin; Valeria Caso; Hanne K Christensen; Rónán Collins; et al. (Translational Stroke Research, 2018)

Temporal heterogeneity increases with spatial heterogeneity in ecological communities - Scott L. Collins; Meghan L. Avolio; Corinna Gries; Lauren M. Hallett; Sally E. Koerner; Kimberly J. La Pierre; Andrew L. Rypel; Eric R. Sokol; Samuel B. Fey; Dan F. B. Flynn; Sydney K. Jones; Laura M. Ladwig; et al. (Ecology, 2018)
Heterogeneity is increasingly recognized as a foundational characteristic of ecological systems. Under global change, understanding temporal community heterogeneity is necessary for predicting the stability of ecosystem functions and services. Indeed, spatial heterogeneity is commonly used in alternative stable state theory as a predictor of temporal heterogeneity and therefore an early indicator of regime shifts. To evaluate whether spatial heterogeneity in species composition is predictive of temporal heterogeneity in ecological communities, we analyzed 68 community data sets spanning freshwater and terrestrial systems where measures of species abundance were replicated over space and time. Of the 68 data sets, 55 (81%) had a weak to strongly positive relationship between spatial and temporal heterogeneity, while in the remaining communities the relationship was weak to strongly negative (19%). Based on a mixed model analysis, we found a significant but weak overall positive relationship between spatial and temporal heterogeneity across all data sets combined, and within aquatic and terrestrial data sets separately. In addition, lifespan and successional stage were negatively and positively related to temporal heterogeneity, respectively. We conclude that spatial heterogeneity may be a predictor of temporal heterogeneity in ecological communities, and that this relationship may be a general property of many terrestrial and aquatic communities.

Modulators of mercury risk to wildlife and humans in the context of rapid global change - Collin A. Eagles-Smith; Ellen K. Silbergeld; Niladri Basu; Paco Bustamante; Fernando Diaz-Barriga; William A. Hopkins; Karen A. Kidd; Jennifer F. Nyland (Ambio, 2018)

Cyclic and Fatigue Behaviour of Rock Materials: Review, Interpretation and Research Perspectives - B. Cerfontaine; F. Collin (Rock Mechanics and Rock Engineering, 2018)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Validation of a New Elastoplastic Constitutive Model Dedicated to the Cyclic Behaviour of Brittle Rock Materials - B. Cerfontaine; R. Charlier; F. Collin; M. Taiebat (Rock Mechanics and Rock Engineering, 2017)

Use of anthropogenic material affects bird nest arthropod community structure: influence of urbanisation, and consequences for ectoparasites and fledging success - Hugh J. Hanmer; Rebecca L. Thomas; Gareth J. F. Beswick; Bradley P. Collins; Mark D. E. Fellowes (Journal of Ornithology, 2017)

Estimation of 3D Ground Reaction Force Using Nanocomposite Piezo-Responsive Foam Sensors During Walking - Parker G. Rosquist; Gavin Collins; A. Jake Merrell; Noelle J. Tuttle; James B. Tracy; Evan T. Bird; Matthew K. Seeley; David T. Fullwood; William F. Christensen; Anton E. Bowden (Annals of Biomedical Engineering, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Invasive planktivores as mediators of organic matter exchanges within and across ecosystems - Scott F. Collins; David H. Wahl (Oecologia, 2017)

Adapting astronomical source detection software to help detect animals in thermal images obtained by unmanned aerial systems - S. N. Longmore; R. P. Collins; S. Pfeifer; S. E. Fox; M. Mulero-Pázmány; F. Bezombes; A. Goodwin; M. De Juan Ovelar; J. H. Knapen; S. A. Wich (International Journal of Remote Sensing, 2017)

Reply to the comments on “Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust” - Rui Wang; William J. Collins; Roberto F. Weinberg; Jeremy P. Richards; Wen-yan He (Contributions to Mineralogy and Petrology, 2017)

Genetic and Manual Survey Methods Yield Different and Complementary Views of an Ecosystem - Ryan P. Kelly; Collin J. Closek; James L. O'Donnell; James E. Kralj; Andrew O. Shelton; Jameal F. Samhouri (Frontiers in Marine Science, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Mapping of seedling resistance in barley to Puccinia striiformis f. sp. pseudohordei - L. N. Kamino; D. Singh; M. A. Pallotta; N. C. Collins; R. F. Park (Journal of Applied Genetics, 2016)

The checkered history of checkerboard distributions: reply - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2015)

A Critical Assessment of the Ecological Assumptions Underpinning Compensatory Mitigation of Salmon-Derived Nutrients - Scott F. Collins; Amy M. Marcarelli; Colden V. Baxter; Mark S. Wipfli (Environmental Management, 2015)

Anthropogenic nitrogen deposition predicts local grassland primary production worldwide - Carly J. Stevens; Eric M. Lind; Yann Hautier; W. Stanley Harpole; Elizabeth T. Borer; Sarah Hobbie; Eric W. Seabloom; Laura Ladwig; Jonathan D. Bakker; Chengjin Chu; Scott Collins; Kendi F. Davies; et al. (Ecology, 2015)
Humans dominate many important Earth system processes including the nitrogen (N) cycle. Atmospheric N deposition affects fundamental processes such as carbon cycling, climate regulation, and biodiversity, and could result in changes to fundamental Earth system processes such as primary production. Both modelling and experimentation have suggested a role for anthropogenically altered N deposition in increasing productivity, nevertheless, current understanding of the relative strength of N deposition with respect to other controls on production such as edaphic conditions and climate is limited. Here we use an international multiscale data set to show that atmospheric N deposition is positively correlated to aboveground net primary production (ANPP) observed at the 1‐m 2 level across a wide range of herbaceous ecosystems. N deposition was a better predictor than climatic drivers and local soil conditions, explaining 16% of observed variation in ANPP globally with an increase of 1 kg N·ha −1 ·yr −1 increasing ANPP by 3%. Soil pH explained 8% of observed variation in ANPP while climatic drivers showed no significant relationship. Our results illustrate that the incorporation of global N deposition patterns in Earth system models are likely to substantially improve estimates of primary production in herbaceous systems. In herbaceous systems across the world, humans appear to be partially driving local ANPP through impacts on the N cycle.

Seismic site characterization of the Kastelli (Kissamos) Basin in northwest Crete (Greece): assessments using ambient noise recordings - M. Moisidi; F. Vallianatos; S. Kershaw; P. Collins (Bulletin of Earthquake Engineering, 2015)

Enhanced characterization of the zebrafish brain as revealed by super-resolution track-density imaging - Jeremy F. P. Ullmann; Fernando Calamante; Shaun P. Collin; David C. Reutens; Nyoman D. Kurniawan (Brain Structure and Function, 2015)

Effects of monsoon precipitation variability on the physiological response of two dominant C4 grasses across a semiarid ecotone - Michell L. Thomey; Scott L. Collins; Michael T. Friggens; Renee F. Brown; William T. Pockman (Oecologia, 2014)

Effects of Chlorpyrifos and Endosulfan on Different Life Stages of the Freshwater Burrowing Crab Zilchiopsis collastinensis P.: Protective Role of Chorion - C. L. Negro; L. E. Senkman; F. Marino; E. Lorenzatti; P. Collins (Bulletin of Environmental Contamination and Toxicology, 2014)

How wide is a stream? Spatial extent of the potential “stream signature” in terrestrial food webs using meta‐analysis - Jeffrey D. Muehlbauer; Scott F. Collins; Martin W. Doyle; Klement Tockner (Ecology, 2014)
The magnitude of cross‐ecosystem resource subsidies is increasingly well recognized; however, less is known about the distance these subsidies travel into the recipient landscape. In streams and rivers, this distance can delimit the “biological stream width,” complementary to hydro‐geomorphic measures (e.g., channel banks) that have typically defined stream ecosystem boundaries. In this study we used meta‐analysis to define a “stream signature” on land that relates the stream‐to‐land subsidy to distance. The 50% stream signature, for example, identifies the point on the landscape where subsidy resources are still at half of their maximum (in‐ or near‐stream) level. The decay curve for these data was best fit by a negative power function in which the 50% stream signature was concentrated near stream banks (1.5 m), but a non‐trivial (10%) portion of the maximum subsidy level was still found >0.5 km from the water's edge. The meta‐analysis also identified explanatory variables that affect the stream signature. This improves our understanding of ecosystem conditions that permit spatially extensive subsidy transmission, such as in highly productive, middle‐order streams and rivers. Resultant multivariate models from this analysis may be useful to managers implementing buffer rules and conservation strategies for stream and riparian function, as they facilitate prediction of the extent of subsidies. Our results stress that much of the subsidy remains near the stream, but also that subsidies (and aquatic organisms) are capable of long‐distance dispersal into adjacent environments, and that the effective “biological stream width” of stream and river ecosystems is often much larger than has been defined by hydro‐geomorphic metrics alone. Limited data available from marine and lake sources overlap well with the stream signature data, indicating that the “signature” approach may also be applicable to subsidy spatial dynamics across other ecosystems.

Infrared analysis for counterfeit electronic parts detection and supply chain validation - E. Thomas Gilmore; Preston D. Frazier; Isaac J. Collins; William Reid; M. F. Chouikha (Environment Systems and Decisions, 2013)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

The checkered history of checkerboard distributions - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2013)
To address the idea that the process of interspecific competition can be inferred from data on geographical distribution alone and that evidence from geographical distribution implies an important role for interspecific competition in shaping ecological communities, we reexamine the occurrence of “true checkerboard” distributions among the land and freshwater birds in three Melanesian archipelagoes: Vanuatu, the Bismarck Archipelago, and the Solomon Islands. We use the most recently published distributional records and explicitly include the geography of the distributions of species within each archipelago. We use the overlap of convex hulls to estimate the overlap in the geographic range for each pair of species in each of these archipelagoes. We define a “true checkerboard” to consist of a pair of species with exclusive island‐by‐island distributions, but that have overlapping geographical ranges. To avoid the “dilution effect,” we follow Diamond and Gilpin in focusing only on congeneric and within‐guild species pairs as potential competitors. Few, if any, “true checkerboards” exist in these archipelagoes that could possibly have been influenced by competitive interactions, and even “true checkerboards” can arise for reasons other than interspecific competition. The similarity between related species pairs (congeneric and within‐guild pairs) and unrelated species pairs in their deviation from expectation of the number of islands shared and the overlap of their geographic ranges indicates that these are not distinct statistical populations, but rather a single population of species pairs. Our result, which is based on an examination of the distributional data alone, is consistent with the interpretation that, in these avifaunas, the distributions of congeneric, within‐guild, and unrelated species pairs are shaped by a common set of biological and physical environmental processes.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Something in the water: biosecurity monitoring of ornamental fish imports using environmental DNA - Rupert A. Collins; Karen F. Armstrong; Andrew J. Holyoake; Suzanne Keeling (Biological Invasions, 2013)

Vegetation–microclimate feedbacks in woodland–grassland ecotones - Paolo D'Odorico; Yufei He; Scott Collins; Stephan F. J. De Wekker; Vic Engel; Jose D. Fuentes (Global Ecology and Biogeography, 2013)
Aim Climatic conditions exert a strong control on the geographic distribution of many woodland‐to‐grassland transition zones (or ‘tree lines’). Because woody plants have, in general, a weaker cold tolerance than herbaceous vegetation, their altitudinal or latitudinal limits are strongly controlled by cold sensitivity. While temperature controls on the dynamics of woodland–grassland ecotones are relatively well established, the ability of woody plants to modify their microclimate and to create habitat for seedling establishment and growth may involve a variety of processes that are still not completely understood. Here we investigate feedbacks between vegetation and microclimatic conditions in the proximity to woodland–grassland ecotones. Location We concentrate on arctic and alpine tree lines, the transition between mangrove forests and salt marshes in coastal ecosystems, and the shift from shrubland to grassland along temperature gradients in arid landscapes. Methods We review the major abiotic and biotic mechanisms underlying the ability of woody plants to alter the nocturnal microclimate by increasing the temperatures they are exposed to. Results We find that in many arctic, alpine, desert and coastal landscapes the presence of trees or shrubs causes nocturnal warming thereby favouring the establishment and survival of woody plants. Main conclusion Because of this feedback, trees and shrubs may establish in areas that would be otherwise unsuitable for their survival. Thus, in grassland–woodland transition zones both vegetation covers may be (alternative) stable states of the landscape, thereby affecting the way tree lines may migrate in response to regional and global climate change.

Population genetics of cobia (Rachycentron canadum) in the Gulf of Thailand and Andaman Sea: fisheries management implications - Jaros Phinchongsakuldit; Puangtip Chaipakdee; James F. Collins; Mullica Jaroensutasinee; John F. Y. Brookfield (Aquaculture International, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Changes in spinal but not cortical excitability following combined electrical stimulation of the tibial nerve and voluntary plantar-flexion - Olle Lagerquist; Cameron S. Mang; David F. Collins (Experimental Brain Research, 2012)

Immunoreactive Hephaestin and ferroxidase activity are present in the cytosolic fraction of rat enterocytes - Perungavur N. Ranganathan; Yan Lu; Brie K. Fuqua; James F. Collins (BioMetals, 2012)

Above- and belowground responses to nitrogen addition in a Chihuahuan Desert grassland - Laura M. Ladwig; Scott L. Collins; Amaris L. Swann; Yang Xia; Michael F. Allen; Edith B. Allen (Oecologia, 2012)

Precipitation variability and fire influence the temporal dynamics of soil CO 2 efflux in an arid grassland - Rodrigo Vargas; Scott L. Collins; Michell L. Thomey; Jennifer E. Johnson; Renee F. Brown; Donald O. Natvig; Michael T. Friggens (Global Change Biology, 2012)
Climate models suggest that extreme rainfall events will become more common with increased atmospheric warming. Consequently, changes in the size and frequency of rainfall will influence biophysical drivers that regulate the strength and timing of soil CO 2 efflux – a major source of terrestrial carbon flux. We used a rainfall manipulation experiment during the summer monsoon season ( J uly– S eptember) to vary both the size and frequency of precipitation in an arid grassland 2 years before and 2 years after a lightning‐caused wildfire. Soil CO 2 efflux rates were always higher under increased rainfall event size than under increased rainfall event frequency, or ambient precipitation. Although fire reduced soil CO 2 efflux rates by nearly 70%, the overall responses to rainfall variability were consistent before and after the fire. The overall sensitivity of soil CO 2 efflux to temperature ( Q 10 ) converged to 1.4, but this value differed somewhat among treatments especially before the fire. Changes in rainfall patterns resulted in differences in the periodicity of soil CO 2 efflux with strong signals at 1, 8, and 30 days. Increased rainfall event size enhanced the synchrony between photosynthetically active radiation and soil CO 2 efflux over the growing season before and after fire, suggesting a change in the temporal availability of substrate pools that regulate the temporal dynamics and magnitude of soil CO 2 efflux. We conclude that arid grasslands are capable of rapidly increasing and maintaining high soil CO 2 efflux rates in response to increased rainfall event size more than increased rainfall event frequency both before and after a fire. Therefore, the amount and pattern of multiple rain pulses over the growing season are crucial for understanding CO 2 dynamics in burned and unburned water‐limited ecosystems.

Phylogeography and bindin evolution in Arbacia , a sea urchin genus with an unusual distribution - H. A. LESSIOS; S. LOCKHART; R. COLLIN; G. SOTIL; P. SANCHEZ‐JEREZ; K. S. ZIGLER; A. F. PEREZ; M. J. GARRIDO; L. B. GEYER; G. BERNARDI; V. D. VACQUIER; R. HAROUN; et al. (Molecular Ecology, 2012)
Among shallow water sea urchin genera, Arbacia is the only genus that contains species found in both high and low latitudes. In order to determine the geographical origin of the genus and its history of speciation events, we constructed phylogenies based on cytochrome oxidase I and sperm bindin from all its species. Both the mitochondrial and the nuclear gene genealogies show that Arbacia originated in the temperate zone of the Southern Hemisphere and gave rise to three species in the eastern Pacific, which were then isolated from the Atlantic by the Isthmus of Panama. The mid‐Atlantic barrier separated two additional species. The bindin data suggest that selection against hybridization is not important in the evolution of this molecule in this genus. Metz et al. in a previous publication found no evidence of selection on bindin of Arbacia and suggested that this might be due to allopatry between species, which obviated the need for species recognition. This suggestion formed the basis of the conclusion, widely spread in the literature, that the source of selection on sea urchin bindin (where it does occur) was reinforcement. However, the range of Arbacia spatuligera overlaps with that of two other species of Arbacia , and our data show that it is hybridizing with one of them. We found that even in the species that overlap geographically, there are no deviations from selective neutrality in the evolution of bindin.

Neuromuscular electrical stimulation: implications of the electrically evoked sensory volley - A. J. Bergquist; J. M. Clair; O. Lagerquist; C. S. Mang; Y. Okuma; D. F. Collins (European Journal of Applied Physiology, 2011)

Neuromuscular electrical stimulation has a global effect on corticospinal excitability for leg muscles and a focused effect for hand muscles - C. S. Mang; J. M. Clair; D. F. Collins (Experimental Brain Research, 2011)

New approaches for the study of osmotic stress induced by polyethylene glycol (PEG) in cereal species - A. Comeau; L. Nodichao; J. Collin; M. Baum; J. Samsatly; D. Hamidou; F. Langevin; A. Laroche; E. Picard (Cereal Research Communications, 2010)

Prey life‐history and bioenergetic responses across a predation gradient - M. D. Rennie; C. F. Purchase; B. J. Shuter; N. C. Collins; P. A. Abrams; G. E. Morgan (Journal of Fish Biology, 2010)
To evaluate the importance of non‐consumptive effects of predators on prey life histories under natural conditions, an index of predator abundance was developed for naturally occurring populations of a common prey fish, the yellow perch Perca flavescens , and compared to life‐history variables and rates of prey energy acquisition and allocation as estimated from mass balance models. The predation index was positively related to maximum size and size at maturity in both male and female P. flavescens , but not with life span or reproductive investment. The predation index was positively related to size‐adjusted specific growth rates and growth efficiencies but negatively related to model estimates of size‐adjusted specific consumption and activity rates in both vulnerable (small) and invulnerable (large) size classes of P. flavescens . These observations suggest a trade‐off between growth and activity rates, mediated by reduced activity in response to increasing predator densities. Lower growth rates and growth efficiencies in populations with fewer predators, despite increased consumption suggests either 1) a reduction in prey resources at lower predator densities or 2) an intrinsic cost of rapid prey growth that makes it unfavourable unless offset by a perceived threat of predation. This study provides evidence of trade‐offs between growth and activity rates induced by predation risk in natural prey fish populations and illustrates how behavioural modification induced through predation can shape the life histories of prey fish species.

Changes in corticospinal excitability evoked by common peroneal nerve stimulation depend on stimulation frequency - C. S. Mang; O. Lagerquist; D. F. Collins (Experimental Brain Research, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Reflex pathways connect receptors in the human lower leg to the erector spinae muscles of the lower back - J. M. Clair; Y. Okuma; J. E. Misiaszek; D. F. Collins (Experimental Brain Research, 2009)

Haplotypes of IL-10 promoter variants are associated with susceptibility to severe malarial anemia and functional changes in IL-10 production - Collins Ouma; Gregory C. Davenport; Tom Were; Michael F. Otieno; James B. Hittner; John M. Vulule; Jeremy Martinson; John M. Ong’echa; Robert E. Ferrell; Douglas J. Perkins (Human Genetics, 2008)

EgAP2-1, an AINTEGUMENTA-like (AIL) gene expressed in meristematic and proliferating tissues of embryos in oil palm - F. Morcillo; A. Gallard; M. Pillot; S. Jouannic; F. Aberlenc-Bertossi; M. Collin; J. L. Verdeil; J. W. Tregear (Planta, 2007)

Determination of Iodine in Low Mass Human Hair Samples by Inductively Coupled Plasma Mass Spectrometry - K. E. Levine; A. S. Essader; F. X. Weber; J. M. Perlmutter; L. S. Milstein; R. A. Fernando; M. A. Levine; B. J. Collins; J. B. Adams; P. M. Grohse (Bulletin of Environmental Contamination and Toxicology, 2007)

Encapsulation of platinum(II)-based DNA intercalators within cucurbit[6,7,8]urils - Sharon Kemp; Nial J. Wheate; Shaoyu Wang; J. Grant Collins; Stephen F. Ralph; Anthony I. Day; Vincent J. Higgins; Janice R. Aldrich-Wright (JBIC Journal of Biological Inorganic Chemistry, 2007)

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A novel locus for autosomal recessive nonsyndromic hearing impairment, DFNB63, maps to chromosome 11q13.2–q13.4 - E. Kalay; R. Caylan; A. F. Kıroglu; T. Yasar; R. W. J. Collin; J. G. A. M. Heister; J. Oostrik; C. W. R. J. Cremers; H. G. Brunner; A. Karaguzel; H. Kremer (Journal of Molecular Medicine, 2007)

Soil carbon pools and fluxes after land conversion in a semiarid shrub-steppe ecosystem - R. L. Cochran; H. P. Collins; A. Kennedy; D. F. Bezdicek (Biology and Fertility of Soils, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Paying for information: partial loads in central place foragers - A. Dornhaus; E. J. Collins; F.-X. Dechaume-Moncharmont; A. I. Houston; N. R. Franks; J. M. McNamara (Behavioral Ecology and Sociobiology, 2006)

Selectivity at a three-base bulge site in the DNA binding of ΔΔ-[{Ru(phen)2}2(μ-dppm)]4+ [dppm is 4,6-bis(2-pyridyl)pyrimidine; phen is 1,10-phenanthroline] - Joy L. Morgan; Damian P. Buck; Adam G. Turley; J. Grant Collins; F. Richard Keene (JBIC Journal of Biological Inorganic Chemistry, 2006)

Diurnal changes in the amplitude of the Hoffmann reflex in the human soleus but not in the flexor carpi radialis muscle - Olle Lagerquist; E. Paul Zehr; Evan R. L. Baldwin; Piotr M. Klakowicz; David F. Collins (Experimental Brain Research, 2006)

Equine CCL11 induces eosinophil cytoskeletal reorganization and activation - M. C. Weston; M. E. Collins; F. M. Cunningham (Inflammation Research, 2006)

Task dependent gain regulation of spinal circuits projecting to the human flexor carpi radialis - Timothy J. Carroll; Evan R. L. Baldwin; David F. Collins (Experimental Brain Research, 2005)

Modulation of cutaneous reflexes in human upper limb muscles during arm cycling is independent of activity in the contralateral arm - Timothy J. Carroll; E. Paul Zehr; David F. Collins (Experimental Brain Research, 2005)

Facilitation of soleus H-reflex amplitude evoked by cutaneous nerve stimulation at the wrist is not suppressed by rhythmic arm movement - E. Paul Zehr; Alain Frigon; Nienke Hoogenboom; David F. Collins (Experimental Brain Research, 2004)

Quantifying the water vapour feedback associated with post-Pinatubo global cooling - P. M. de F. Forster; M. Collins (Climate Dynamics, 2004)

Predictability of Indian Ocean sea surface temperature using canonical correlation analysis - D. C. Collins; C. J. C. Reason; F. Tangang (Climate Dynamics, 2004)

The SLC20 family of proteins: dual functions as sodium-phosphate cotransporters and viral receptors - James F. Collins; Liqun Bai; Fayez K. Ghishan (Pflügers Archiv - European Journal of Physiology, 2004)

Mexican American ancestry-informative markers: examination of population structure and marker characteristics in European Americans, Mexican Americans, Amerindians and Asians - Heather E. Collins-Schramm; Robert L. Hanson; William C. Knowler; Gabriel Silva; Michael F. Seldin; Bill Chima; Takanobu Morii; Kimberly Wah; Yolanda Figueroa; Lindsey A. Criswell; John W. Belmont (Human Genetics, 2004)

Molecular evolutionary analysis of the widespread piggyBac transposon family and related "domesticated" sequences - A. Sarkar; C. Sim; Y. S. Hong; J. R. Hogan; M. J. Fraser; H. M. Robertson; F. H. Collins (Molecular Genetics and Genomics, 2003)

Markers informative for ancestry demonstrate consistent megabase-length linkage disequilibrium in the African American population - Michael F. Seldin; Heather E. Collins-Schramm; Bill Chima; Darwin J. Operario; Lindsey A. Criswell (Human Genetics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Parabolic Equation Techniques for Seismic Waves - W. Jerzak; M. D. Collins; R. B. Evans; J. F. Lingevitch; W. L. Siegmann (Pure and Applied Geophysics, 2002)

Human interlimb reflexes evoked by electrical stimulation of cutaneous nerves innervating the hand and foot - Paul E. Zehr; David F. Collins; Romeo Chua (Experimental Brain Research, 2001)

An Assessment of HOx Chemistry in the Tropical Pacific Boundary Layer: Comparison of Model Simulations with Observations Recorded during PEM Tropics A - G. Chen; D. Davis; J. Crawford; B. Heikes; D. O'Sullivan; M. Lee; F. Eisele; L. Mauldin; D. Tanner; J. Collins; J. Barrick; B. Anderson; et al. (Journal of Atmospheric Chemistry, 2001)

The internal climate variability of HadCM3, a version of the Hadley Centre coupled model without flux adjustments - M. Collins; S. F. B. Tett; C. Cooper (Climate Dynamics, 2001)

Glucosinolates and Differential Herbivory in Wild Populations of Brassica oleracea - Catherine L. Moyes; Hamish A. Collin; George Britton; Alan F. Raybould (Journal of Chemical Ecology, 2000)

The isolation and characterization of microsatellites from Anopheles dirus mosquitoes - C. Walton; M. S. Chang; J. M. Handley; R. E. Harbach; F. H. Collins; V. Baimai; R. K. Butlin (Molecular Ecology, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

The presence of cross-reactive antibodies to rabbit haemorrhagic disease virus in Australian wild rabbits prior to the escape of virus from quarantine - H. S. Nagesha; K. A. McColl; B. J. Collins; C. J. Morrissy; L. -F. Wang; H. A. Westbury (Archives of Virology, 2000)

Isolation of polymorphic microsatellite loci from the malaria vector Anopheles funestus - S. P. Sinkins; B. J. Hackett; C. Costantini; J. Vulule; Y‐Y. Ling; F. H. Collins; N. J. Besansky (Molecular Ecology, 2000)

Surface Water Transport of Lead at a Shooting Range - J. R. Craig; J. D. Rimstidt; C. A. Bonnaffon; T. K. Collins; P. F. Scanlon (Bulletin of Environmental Contamination and Toxicology, 1999)

The synthesis and spectroscopic analysis of the neurotoxic prion peptide 106–126: Comparative use of manual Boc and Fmoc chemistry - Michael F. Jobling; Colin J. Barrow; Anthony R. White; Colin L. Masters; Steven J. Collins; Roberto Cappai (International Journal of Peptide Research and Therapeutics, 1999)

Muscle parvalbumin isoforms of Clarias gariepinus, Heterobranchus longifilis and Chrysichthys auratus : isolation, characterization and expression during development - B. Focant; F. Mélot; S. Collin; A. Chikou; P. Vandewalle; F. Huriaux (Journal of Fish Biology, 1999)
The white‐muscle parvalbumin isoforms of Clarias gariepinus, Heterobranchus longifilis and Chrysichthys auratus were purified and their physicochemical parameters determined. The three catfish isoforms are distinct but those of C. gariepinus and H. longifilis are more similar. In the course of development, the successive appearance of larval and adult parvalbumins was observed. Larval isoforms (PA I, PA IIa, PA IIb) displayed a lower isoelectric point (pI) and molecular mass than adult ones (PA IIc, PA IIIa, PA IIIb, PA III, PA IV). The PA IIa isoform appeared as an omnipresent typical larval isoform. PA IIb appeared mostly larval, being insignificant in adult specimens; its physicochemical features were the same in the three catfish species. In Chrysichthys auratus , there were three PA II isoforms, one appearing as an adult isoform (PA IIc). The fact that the two types of parvalbumin isoforms appear at different times should reflect specific physiological needs (mobility, feeding) of different developmental stages.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Impacts of Elevated Carbon Dioxide and Temperature on a Boreal Forest Ecosystem (CLIMEX Project) - Nico van Breemen; Alan Jenkins; Richard F. Wright; David J. Beerling; Wim J. Arp; Frank Berendse; Claus Beier; Rob Collins; Douwe van Dam; Lennart Rasmussen; Paul S. J. Verburg; Mark A. Wills (Ecosystems, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Characterization of parvalbumin isotypes in white muscle from the barbel and expression during development - F. Huriaux; S. Collin; P. Vandewalle; J. C. Philippart; B. Focant (Journal of Fish Biology, 1997)
Parvalbumin isotypes PA II, PA III, PA IVa, and PA IVb were isolated by chromatography from trunk white muscle of barbel and physicochemically characterized. Electrospray ionization mass spectroscopy revealed that PA II has a lower molecular weight than the other isotypes and that PA IVa and PA IVb each consist of two subforms. Isotype distribution was studied by polyacrylamide gel electrophoresis. In adult fish, the total parvalbumin titre decreased and the isotype distribution varied from the anterior to the posterior myotomes. In the course of barbel development, the total parvalbumin titre increased rapidly as fish standard length increased from 1·3 to 5 cm; then sloped down gently as the length increased to 60 cm. At least six parvalbumin isotypes were identified, three of which are different forms (a, b, and c) of PA II. These three forms were present together at the larval stage, but PA IIc and chiefly PA IIb appeared as early isotypes, contrary to PA IIa which was present until the adult period. Later PA IVb accounted for up to 90% of the total parvalbumin content; PA III and PA IVa are minor adult isotypes. Temporal and spatial variations in the total parvalbumin titre and in the differential expression of barbel parvalbumin isotypes very likely reflected the functional requirements of the fish axial musculature according to fish size and myotome location. Physiologically, the larval isotypes could promote faster relaxation of fast fibres than the adult isotypes, and hence favour shorter contraction times.

Microgeographic structure of Anopheles gambiae in western Kenya based on mtDNA and microsatellite loci - T. Lehmann; N. J. Besansky; W. A. Hawley; T. G. Fahey; L. Kamau; F. H. Collins (Molecular Ecology, 1997)
The population genetic structure of the Anopheles gambiae in western Kenya was studied using length variation at five microsatellite loci and sequence variation in a 648‐nt mtDNA fragment. Mosquitoes were collected from houses in villages spanning up to 50 km distance, The following questions were answered, (i) Are mosquitoes in a house more related genetically to each other than mosquitoes between houses? (ii) What degree of genetic differentiation occurs on these geographical scales? (iii) How consistent are the results obtained with both types of genetic markers? At the house level, no differentiation was detected by F ST and R ST , and the band sharing index test revealed no significant associations of alleles across loci. Likewise, indices of kinship based on mtDNA haplotypes in houses were even lower than in the pooled sample. Therefore, the hypothesis that mosquitoes in a house are more related genetically was rejected. At increasing geographical scales, microsatellite allele distributions were similar among all population samples and no subdivision of the gene pool was detected by F ST or R ST . Likewise, estimates of haplotype divergence of mtDNA between populations were not higher than the within population estimates, and mtDNA‐based F ST values were not significantly different from zero. That sequence variation in mtDNA provided matching results with microsatellite loci (while high genetic variation was observed in all loci), suggested that this pattern represents the whole genome. The minimum area associated with a deme of A. gambiae in western Kenya is therefore larger than 50 km in diameter.

Cloning of the human NADH: ubiquinone oxidoreductase subunit B13: Localization to Chromosome 7q32 and identification of a pseudogene on 11pl5 - M. W. Russell; S. du Manoir; F. S. Collins; L. C. Brody (Mammalian Genome, 1997)

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Late Devensian river and floodplain dynamics and related environmental change in northwest Europe, with particular reference to a site at Woolhampton, Berkshire, England - PHILIP E. F. COLLINS; IAN M. FENWICK; D. MICHAEL KEITH-LUCAS; PETER WORSLEY (Journal of Quaternary Science, 1996)

Cloning and nucleotide sequence of the capsid protein and the nuclear inclusion protein (NIb) of potato virus A - R. F. Collins; D. Leclerc; M. G. AbouHaidar (Archives of Virology, 1993)

Characterization of paramyxoviruses isolated from penguins in Antarctica and sub-Antarctica during 1976?1979 - D. J. Alexander; R. J. Manvell; M. S. Collins; S. J. Brockman; H. A. Westbury; I. Morgan; F. J. Austin (Archives of Virology, 1989)

Properties of a newly isolated, serologically distinct avian paramyxovirus - D. J. Alexander; K. F. Shortridge; M. S. Collins; N. J. Chettle (Archives of Virology, 1979)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Multiple molecular forms of xanthine dehydrogenase and related enzymes. IV. The relationship of aldehyde oxidase to xanthine dehydrogenase - J. F. Collins; E. J. Duke; E. Glassman (Biochemical Genetics, 1971)